Resin composition

The resin composition, comprising epoxy resin, (meth)acrylic acid ester, a haloing inhibitor, and an inorganic filler, addresses the challenges of achieving low dielectric loss tangents and suppressing haloing in printed wiring boards, resulting in enhanced adhesion and reliability.

JP7655692B2Active Publication Date: 2025-04-02AJINOMOTO CO INC
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2018101770
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2018-05-28
Publication Date
2025-04-02
Estimated Expiration
2038-05-28

AI Technical Summary

Technical Problem

Existing resin compositions for forming insulating layers in printed wiring boards struggle to achieve low dielectric loss tangents while suppressing the haloing phenomenon, which leads to delamination and reduced conductivity, especially in finer and higher density wiring applications.

Method used

A resin composition comprising a combination of epoxy resin, (meth)acrylic acid ester, a haloing inhibitor, and an inorganic filler, which together provide a low dielectric loss tangent and effectively suppress the haloing phenomenon, enhancing adhesion between the resin layer and the conductor layer.

Benefits of technology

The proposed resin composition achieves a low dielectric loss tangent and significantly suppresses the haloing phenomenon, resulting in improved adhesion and reliability of the insulating layers in printed wiring boards, even in high-density and fine-pitch applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007655692000013
    Figure 0007655692000013
  • Figure 0007655692000014
    Figure 0007655692000014
  • Figure 0007655692000015
    Figure 0007655692000015
Patent Text Reader

Abstract

To provide a resin composition that makes it possible to obtain a cured product that has a low dielectric loss tangent and prevents the holoing phenomenon; a resin sheet containing the resin composition; a printed wiring board including an insulating layer formed with the resin composition; and a semiconductor device.SOLUTION: A resin composition contains (A) an epoxy resin, (B) a (meth) acrylate, (C) a holoing inhibitor, and (D) inorganic filler.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition. The present invention further relates to a resin sheet, a printed wiring board, and a semiconductor device each containing the resin composition. [Background technology]

[0002] A known manufacturing technique for printed wiring boards is a build-up method in which insulating layers and conductor layers are alternately stacked on an inner layer circuit board. Insulating layers are generally formed by curing a resin composition. For example, Patent Document 1 describes a resin composition containing (A) a radical polymerizable compound, (B) an epoxy resin, (C) a curing agent, and (D) a roughening component. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2014-034580 A Summary of the Invention [Problem to be solved by the invention]

[0004] Many resin compositions suitable for forming insulating layers of inner layer circuit boards have been proposed, including the resin composition described in Patent Document 1. However, in recent years, there has been an increasing demand for insulating layers with low dielectric tangents.

[0005] As a result of the study by the present inventor, it has been found that the cured product of the resin composition containing a material that lowers the dielectric tangent causes a haloing phenomenon that reduces the conduction reliability. In recent years, when manufacturing a multilayer printed wiring board, the cured product of the resin composition for forming the insulating layer is required to have a low dielectric tangent and conduction reliability even when the wiring is finer and denser, but these requirements have not been fully met at present. Here, the haloing phenomenon refers to the occurrence of interlayer peeling between the insulating layer and the inner layer substrate around the via hole. Such a haloing phenomenon usually occurs when the resin around the via hole deteriorates during the formation of the via hole, and the deteriorated part is eroded during the roughening treatment. The deteriorated part is usually observed as a discolored part.

[0006] An object of the present invention is to provide a resin composition capable of giving a cured product having a low dielectric tangent and capable of suppressing the haloing phenomenon; a resin sheet containing the resin composition; a printed wiring board having an insulating layer formed using the resin composition; and a semiconductor device including the printed wiring board. [Means for solving the problem]

[0007] Means for Solving the Problems The present inventors have conducted intensive research to solve the above-mentioned problems, and as a result have found that the above-mentioned problems can be solved by a resin composition containing in combination (A) an epoxy resin, (B) a (meth)acrylic acid ester, (C) a haloing inhibitor, and (D) an inorganic filler, and have thus completed the present invention. That is, the present invention includes the following.

[0008] [1] (A) epoxy resin, (B) a (meth)acrylic acid ester, (C) a haloing inhibitor, and (D) A resin composition comprising an inorganic filler. [2] The resin composition according to [1], wherein the component (C) is one or more selected from the group consisting of rust inhibitors, antioxidants, light stabilizers, and colorants. [3] The resin composition according to [1] or [2], wherein the content of component (C) is 0.01% by mass or more and 10% by mass or less, when the total amount of non-volatile components in the resin composition is 100% by mass. [4] The resin composition according to any one of [1] to [3], wherein the content of component (B) is 0.1% by mass or more and 10% by mass or less, when the total amount of non-volatile components in the resin composition is 100% by mass. [5] The resin composition according to any one of [1] to [4], wherein the component (B) has a cyclic structure. [6] The resin composition according to any one of [1] to [5], wherein the component (B) has a structure represented by the following formula (B-1): [ka] (In formula (B-1), R 1 and R 4 each independently represents an acryloyl group or a methacryloyl group, R 2 and R 3 each independently represents a divalent linking group. Ring A represents a divalent cyclic group. [7] The resin composition according to any one of [1] to [6], further comprising (E) a curing agent. [8] The resin composition according to [7], wherein the component (E) is one or more selected from the group consisting of benzoxazine-based curing agents, carbodiimide-based curing agents, phenol-based curing agents, and active ester-based curing agents. [9] The resin composition according to any one of [1] to [8], for use in insulating applications.

[10] The resin composition according to any one of [1] to [9], which is for forming an insulating layer.

[11] The resin composition according to any one of [1] to

[10] , which is for forming an insulating layer for forming a conductor layer.

[12] The resin composition according to any one of [1] to

[11] , which is used for encapsulating a semiconductor chip.

[13] A resin sheet comprising a support and a resin composition layer provided on the support, the resin composition layer comprising the resin composition according to any one of [1] to

[12] .

[14] A printed wiring board comprising an insulating layer formed from a cured product of the resin composition according to any one of [1] to

[12] .

[15] A semiconductor device comprising the printed wiring board according to

[14] . Effect of the Invention

[0009] According to the present invention, there are provided a resin composition capable of giving a cured product having a low dielectric tangent and capable of suppressing the haloing phenomenon; a resin sheet containing the resin composition; a printed wiring board having an insulating layer formed using the resin composition; and a semiconductor device including the printed wiring board. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a cross-sectional view showing a schematic view of an insulating layer obtained by curing the resin composition of the present invention into a sheet shape, together with an inner layer substrate. [Diagram 2] FIG. 2 is a plan view showing a schematic view of the surface of an insulating layer obtained by curing the resin composition of the present invention into a sheet shape, the surface being opposite to the conductive layer. [Diagram 3] FIG. 3 is a cross-sectional view showing a roughening-treated insulating layer obtained by curing the resin composition of the present invention into a sheet shape, together with an inner layer substrate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The present invention will be described in detail below with reference to the following embodiments and examples. However, the present invention is not limited to the following embodiments and examples, and may be modified and implemented as desired without departing from the scope of the claims of the present invention and their equivalents.

[0012] [Resin composition] The resin composition of the present invention is a resin composition containing (A) an epoxy resin, (B) a (meth)acrylic acid ester, (C) a haloing inhibitor, and (D) an inorganic filler. By using such a resin composition, the desired effect of the present invention can be obtained, that is, a cured product having a low dielectric tangent and excellent suppression of the haloing phenomenon can be obtained. Furthermore, by using such a resin composition, it is usually possible to increase the adhesion between the conductor layer.

[0013] The resin composition may further contain optional components in combination with the components (A) to (D). Examples of the optional components include a curing agent (E), a curing accelerator (F), a polymerization initiator (G), a thermoplastic resin (H), a flame retardant (I), and other additives (J). Each component contained in the resin composition will be described in detail below.

[0014] <(A) Epoxy resin> Examples of the epoxy resin (A) include bixylenol type epoxy resin, bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol S type epoxy resin, bisphenol AF type epoxy resin, dicyclopentadiene type epoxy resin, trisphenol type epoxy resin, naphthol novolac type epoxy resin, phenol novolac type epoxy resin, tert-butyl-catechol type epoxy resin, naphthalene type epoxy resin, naphthol type epoxy resin, anthracene type epoxy resin, glycidylamine type epoxy resin, glycidyl ester type epoxy resin, cresol novolac type epoxy resin, biphenyl type epoxy resin, linear aliphatic epoxy resin, epoxy resin having a butadiene structure, alicyclic epoxy resin, heterocyclic epoxy resin, spiro ring-containing epoxy resin, cyclohexane type epoxy resin, cyclohexane dimethanol type epoxy resin, naphthylene ether type epoxy resin, trimethylol type epoxy resin, tetraphenylethane type epoxy resin, etc. The epoxy resin may be used alone or in combination of two or more types.

[0015] The resin composition preferably contains, as the epoxy resin (A), an epoxy resin having two or more epoxy groups in one molecule. From the viewpoint of significantly obtaining the desired effects of the present invention, the proportion of the epoxy resin having two or more epoxy groups in one molecule is preferably 50% by mass or more, more preferably 60% by mass or more, and particularly preferably 70% by mass or more, based on 100% by mass of the non-volatile components of the epoxy resin (A).

[0016] Epoxy resins include epoxy resins that are liquid at a temperature of 20° C. (hereinafter sometimes referred to as "liquid epoxy resins") and epoxy resins that are solid at a temperature of 20° C. (hereinafter sometimes referred to as "solid epoxy resins"). The resin composition may contain only liquid epoxy resins or only solid epoxy resins as the epoxy resin (A), but it is preferable to contain a combination of liquid epoxy resins and solid epoxy resins. By using a combination of liquid epoxy resins and solid epoxy resins as the epoxy resin (A), sufficient flexibility can be obtained when used in the form of a resin sheet, and the breaking strength of the cured product of the resin composition can be improved.

[0017] The liquid epoxy resin is preferably a liquid epoxy resin having two or more epoxy groups in one molecule.

[0018] As the liquid epoxy resin, bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol AF type epoxy resin, naphthalene type epoxy resin, glycidyl ester type epoxy resin, glycidyl amine type epoxy resin, phenol novolac type epoxy resin, alicyclic epoxy resin having an ester skeleton, cyclohexane type epoxy resin, cyclohexane dimethanol type epoxy resin, glycidyl amine type epoxy resin, and epoxy resin having a butadiene structure are preferred, and bisphenol A type epoxy resin is more preferred.

[0019] Specific examples of liquid epoxy resins include "HP4032", "HP4032D", and "HP4032SS" (naphthalene type epoxy resins) manufactured by DIC Corporation; "828US", "jER828EL", "825", and "Epikote 828EL" (bisphenol A type epoxy resins) manufactured by Mitsubishi Chemical Corporation; "jER807" and "1750" (bisphenol F type epoxy resins) manufactured by Mitsubishi Chemical Corporation; "jER152" (phenol novolac type epoxy resin) manufactured by Mitsubishi Chemical Corporation; and "630" and "630LSD" (glycidylamine type epoxy resins) manufactured by Mitsubishi Chemical Corporation. epoxy resin); "ZX1059" manufactured by Nippon Steel & Sumitomo Metal Chemical Co., Ltd. (a mixture of bisphenol A type epoxy resin and bisphenol F type epoxy resin); "EX-721" manufactured by Nagase ChemteX Corporation (glycidyl ester type epoxy resin); "Celloxide 2021P" manufactured by Daicel Corporation (alicyclic epoxy resin having an ester skeleton); "PB-3600" manufactured by Daicel Corporation (epoxy resin having a butadiene structure); "ZX1658" and "ZX1658GS" (liquid 1,4-glycidylcyclohexane type epoxy resin) manufactured by Nippon Steel & Sumitomo Metal Chemical Co., Ltd. may be used alone or in combination of two or more types.

[0020] As the solid epoxy resin, a solid epoxy resin having three or more epoxy groups in one molecule is preferable, and an aromatic solid epoxy resin having three or more epoxy groups in one molecule is more preferable.

[0021] As the solid epoxy resin, bixylenol type epoxy resin, naphthalene type epoxy resin, naphthalene type tetrafunctional epoxy resin, cresol novolac type epoxy resin, dicyclopentadiene type epoxy resin, trisphenol type epoxy resin, naphthol type epoxy resin, biphenyl type epoxy resin, naphthylene ether type epoxy resin, anthracene type epoxy resin, bisphenol A type epoxy resin, bisphenol AF type epoxy resin, and tetraphenylethane type epoxy resin are preferred, and bisphenol AF type epoxy resin, biphenyl type epoxy resin, and bixylenol type epoxy resin are more preferred.

[0022] Specific examples of solid epoxy resins include "HP4032H" (naphthalene type epoxy resin) manufactured by DIC Corporation; "HP-4700" and "HP-4710" (naphthalene type tetrafunctional epoxy resins) manufactured by DIC Corporation; "N-690" (cresol novolac type epoxy resin) manufactured by DIC Corporation; "N-695" (cresol novolac type epoxy resin) manufactured by DIC Corporation; "HP-7200" (dicyclopentadiene type epoxy resin) manufactured by DIC Corporation; "HP-7200HH", "HP-7200H", "EXA-7311", "EXA-7311-G3", and "EXA-7311- G4, EXA-7311-G4S, HP6000 (naphthylene ether type epoxy resin); EPPN-502H (trisphenol type epoxy resin) manufactured by Nippon Kayaku Co., Ltd.; NC7000L (naphthol novolac type epoxy resin) manufactured by Nippon Kayaku Co., Ltd.; NC3000H, NC3000, NC3000L, NC3100 (biphenyl type epoxy resin) manufactured by Nippon Kayaku Co., Ltd.; ESN475V (naphthol type epoxy resin) manufactured by Nippon Steel & Sumitomo Metal Chemical Co., Ltd.; ESN485 (naphthol novolac type epoxy resin) manufactured by Nippon Steel & Sumitomo Metal Chemical Co., Ltd.; Mitsubishi Chemical Co., Ltd. of" YL6121" (biphenyl type epoxy resin); manufactured by Mitsubishi Chemical Corporation "YX4000H", "YX4000", Examples of such epoxy resins include "YX4000HK" (bixylenol type epoxy resin); "YX8800" (anthracene type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "PG-100" and "CG-500" manufactured by Osaka Gas Chemicals Co., Ltd.; "YL7760" (bisphenol AF type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "YL7800" (fluorene type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "jER1010" (solid bisphenol A type epoxy resin) manufactured by Mitsubishi Chemical Corporation; and "jER1031S" (tetraphenylethane type epoxy resin) manufactured by Mitsubishi Chemical Corporation. These may be used alone or in combination of two or more types.

[0023] When a liquid epoxy resin and a solid epoxy resin are used in combination as the (A) epoxy resin, the ratio of the amounts thereof (liquid epoxy resin:solid epoxy resin) is preferably 1:1 to 1:20, more preferably 1:1.5 to 1:15, and particularly preferably 1:2 to 1:10, by mass. When the ratio of the liquid epoxy resin to the solid epoxy resin is within such a range, the desired effects of the present invention can be significantly obtained. Furthermore, when used in the form of a resin sheet, appropriate adhesion is usually obtained. Furthermore, when used in the form of a resin sheet, sufficient flexibility is usually obtained, and handling is improved. Furthermore, a cured product having sufficient breaking strength can usually be obtained.

[0024] The epoxy equivalent of the (A) epoxy resin is preferably 50 g / eq to 5000 g / eq, more preferably 50 g / eq to 3000 g / eq, even more preferably 80 g / eq to 2000 g / eq, and even more preferably 110 g / eq to 1000 g / eq. When it is in this range, the crosslink density of the cured product of the resin composition layer is sufficient, and an insulating layer with small surface roughness can be obtained. The epoxy equivalent is the mass of a resin containing one equivalent of an epoxy group. This epoxy equivalent can be measured according to JIS K7236.

[0025] The weight average molecular weight (Mw) of the (A) epoxy resin is preferably 100 to 5,000, more preferably 250 to 3,000, and even more preferably 400 to 1,500, from the viewpoint of significantly achieving the desired effects of the present invention. The weight average molecular weight of the resin can be measured by gel permeation chromatography (GPC) as a polystyrene-equivalent value.

[0026] The content of the (A) epoxy resin is preferably 1% by mass or more, more preferably 3% by mass or more, and even more preferably 5% by mass or more, based on 100% by mass of the non-volatile components in the resin composition, from the viewpoint of obtaining an insulating layer exhibiting good mechanical strength and insulating reliability. The upper limit of the content of the epoxy resin is preferably 30% by mass or less, more preferably 25% by mass or less, and particularly preferably 20% by mass or less, from the viewpoint of significantly obtaining the desired effects of the present invention. In the present invention, the content of each component in the resin composition is the value based on 100% by mass of the non-volatile components in the resin composition, unless otherwise specified.

[0027] <(B) (Meth)acrylic acid ester> The resin composition contains (B) a (meth)acrylic acid ester. By including (B) a (meth)acrylic acid ester in the resin composition, it is possible to obtain a cured product having a low dielectric tangent. Here, the term "(meth)acrylic acid" includes acrylic acid, methacrylic acid, and a combination thereof.

[0028] From the viewpoint of obtaining a cured product having a low dielectric tangent, the (B) (meth)acrylic acid ester preferably has two or more (meth)acryloyl groups per molecule. The term "(meth)acryloyl group" includes an acryloyl group, a methacryloyl group, and a combination thereof.

[0029] (B) (meth)acrylic acid ester preferably has a cyclic structure from the viewpoint of obtaining a cured product having a low dielectric tangent. The cyclic structure is preferably a divalent cyclic group. The divalent cyclic group may be either a cyclic group containing an alicyclic structure or a cyclic group containing an aromatic ring structure. Among them, from the viewpoint of significantly obtaining the desired effect of the present invention, a cyclic group containing an alicyclic structure is preferable.

[0030] From the viewpoint of significantly obtaining the desired effects of the present invention, the divalent cyclic group is preferably a 3-membered or larger ring, more preferably a 4-membered or larger ring, and even more preferably a 5-membered or larger ring, and is preferably a 20-membered or smaller ring, more preferably a 15-membered or smaller ring, and even more preferably a 10-membered or smaller ring. In addition, the divalent cyclic group may be a monocyclic structure or a polycyclic structure.

[0031] The ring in the divalent cyclic group may have a ring skeleton constituted by a heteroatom other than carbon atoms. Examples of the heteroatom include an oxygen atom, a sulfur atom, and a nitrogen atom, and an oxygen atom is preferred. The ring may have one or more heteroatoms.

[0032] Specific examples of the divalent cyclic group include the following divalent groups (i) to (xi). Among them, the divalent cyclic group is preferably (x) or (xi). [ka]

[0033] The divalent cyclic group may have a substituent, such as a halogen atom, an alkyl group, an alkoxy group, an aryl group, an arylalkyl group, a silyl group, an acyl group, an acyloxy group, a carboxy group, a sulfo group, a cyano group, a nitro group, a hydroxy group, a mercapto group, or an oxo group, and an alkyl group is preferred.

[0034] The (meth)acryloyl group may be directly bonded to the divalent cyclic group, or may be bonded via a divalent linking group. Examples of the divalent linking group include an alkylene group, an alkenylene group, an arylene group, a heteroarylene group, -C(=O)O-, -O-, -NHC(=O)-, -NC(=O)N-, -NHC(=O)O-, -C(=O)-, -S-, -SO-, -NH-, and the like, and may be a group in which a plurality of these are combined. The alkylene group is preferably an alkylene group having 1 to 10 carbon atoms, more preferably an alkylene group having 1 to 6 carbon atoms, and even more preferably an alkylene group having 1 to 5 carbon atoms or an alkylene group having 1 to 4 carbon atoms. The alkylene group may be linear, branched, or cyclic. Examples of such alkylene groups include methylene, ethylene, propylene, butylene, pentylene, hexylene, and 1,1-dimethylethylene groups, and are preferably methylene, ethylene, or 1,1-dimethylethylene. As the alkenylene group, an alkenylene group having 2 to 10 carbon atoms is preferred, an alkenylene group having 2 to 6 carbon atoms is more preferred, and an alkenylene group having 2 to 5 carbon atoms is even more preferred. As the arylene group or heteroarylene group, an arylene group or heteroarylene group having 6 to 20 carbon atoms is preferred, and an arylene group or heteroarylene group having 6 to 10 carbon atoms is more preferred. As the divalent linking group, an alkylene group is preferred, and among them, a methylene group or a 1,1-dimethylethylene group is preferred.

[0035] The (B) (meth)acrylic acid ester is preferably represented by the following formula (B-1). [ka] (In formula (B-1), R 1 and R 4 each independently represents an acryloyl group or a methacryloyl group, R 2 and R 3 each independently represents a divalent linking group. Ring A represents a divalent cyclic group.

[0036] R 1 and R 4each independently represents an acryloyl group or a methacryloyl group, and an acryloyl group is preferred.

[0037] R 2 and R 3 each independently represents a divalent linking group. The divalent linking group is the same as the divalent linking group described above.

[0038] Ring A represents a divalent cyclic group. Ring A is the same as the above divalent cyclic group.

[0039] Ring A may have a substituent. The substituent is the same as the substituent that the above divalent cyclic group may have.

[0040] Specific examples of the component (B) are shown below, but the present invention is not limited to these. [ka]

[0041] The (B) component may be a commercially available product, for example, "NK Ester A-DOG" ((meth)acryloyl group equivalent 163) manufactured by Shin-Nakamura Chemical Co., Ltd., "DCP-A" ((meth)acryloyl group equivalent 152) manufactured by Kyoeisha Chemical Co., Ltd., "NPDGA" ((meth)acryloyl group equivalent 106), "FM-400" ((meth)acryloyl group equivalent 156), "R-687" ((meth)acryloyl group equivalent 187), "THE-330" ((meth)acryloyl group equivalent 143), "PET-30" ((meth)acryloyl group equivalent 88), "DPHA" ((meth)acryloyl group equivalent 96), etc. may be mentioned. The (B) component may be used alone or in combination of two or more types.

[0042] From the viewpoint of obtaining a cured product with a low dielectric tangent, the (meth)acryloyl group equivalent of the (B) component is preferably 30 g / eq. to 400 g / eq., more preferably 50 g / eq. to 300 g / eq., and even more preferably 75 g / eq. to 200 g / eq. The (meth)acryloyl group equivalent is the mass of the (B) component containing one equivalent of a (meth)acryloyl group.

[0043] The content of the (B) component is preferably 0.1% by mass or more, more preferably 1% by mass or more, and even more preferably 1.5% by mass or more, based on 100% by mass of the non-volatile components in the resin composition, from the viewpoint of obtaining a cured product with a low dielectric tangent and excellent adhesion. The upper limit is preferably 10% by mass or less, more preferably 8% by mass or less, and even more preferably 5% by mass or less, based on the viewpoint of suppressing the haloing phenomenon.

[0044] <(C) Haloing inhibitor> The resin composition contains a haloing suppressant (C). By including the haloing suppressant (C) in the resin composition, it is possible to obtain a cured product in which haloing is suppressed. Here, the haloing suppressant (C) refers to a compound that absorbs light energy such as laser light. By including the haloing suppressant (C) in the resin composition, when a via hole is formed in the cured product of the resin composition formed on the inner layer substrate using a laser light, the haloing suppressant (C) absorbs the light energy of the laser light. Therefore, as the depth of the via hole increases, the light energy becomes weaker, and deterioration of the resin around the inner layer substrate is suppressed. As a result, it is considered possible to suppress delamination occurring between the insulating layer and the inner layer substrate.

[0045] The (C) haloing inhibitor may contain a compound capable of absorbing laser light. For example, the (C) component is preferably a compound having one or more compounds selected from the group consisting of unsaturated groups such as carbon-carbon double bonds, carbon-nitrogen double bonds, nitrogen-nitrogen double bonds, and carbonyl groups; and aromatic rings. Specific examples of such compounds include one or more compounds selected from the group consisting of rust inhibitors, antioxidants, light stabilizers, and colorants.

[0046] -Rust inhibitor- The rust inhibitor may be an amine compound, an azole compound consisting of imidazole, triazole, tetrazole, benzotriazole and their derivatives, a nitrite salt, an ammonium salt, etc. Among them, from the viewpoint of obtaining the effect of the present invention remarkably, an azole compound is preferable as the rust inhibitor. The rust inhibitor may be a commercially available product.

[0047] Specific examples of the rust inhibitor include 1,2,3-benzotriazole (manufactured by Johoku Chemical Industry Co., Ltd., BT120), 1-[N,N-bis(2-ethylhexyl)aminomethyl]benzotriazole (manufactured by Johoku Chemical Industry Co., Ltd., BT-LX), carboxybenzotriazole (manufactured by Johoku Chemical Industry Co., Ltd., CBT-1), 1-[N,N-bis(2-ethylhexyl)aminomethyl]methylbenzotriazole (manufactured by Johoku Chemical Industry Co., Ltd., TT-LX), 2,2′-[[(methyl-1H-benzotriazol-1-yl)methyl]imino]bisethanol (manufactured by Johoku Chemical Industry Co., Ltd. Examples of such benzotriazole include 1-(1',2'-dicarboxyethyl)benzotriazole (Johoku Chemical Industry Co., Ltd., TT-LYK), 1-(1',2'-dicarboxyethyl)benzotriazole (Johoku Chemical Industry Co., Ltd., BT-M), 1-(2,3-dicarboxypropyl)benzotriazole (Johoku Chemical Industry Co., Ltd., BT-250), 1-(2-ethylhexylaminomethyl)benzotriazole (Johoku Chemical Industry Co., Ltd., BT-260), 2,6-bis[(1H-benzotriazol-1-yl)methyl]-4-methylphenol (Johoku Chemical Industry Co., Ltd., BT-3700), and 5-methylbenzotriazole (Johoku Chemical Industry Co., Ltd., 5M-BTA).

[0048] -Antioxidants- Examples of the antioxidant include hindered phenol-based antioxidants, phosphorus-based antioxidants, and sulfur-based antioxidants. Among them, from the viewpoint of obtaining the effects of the present invention remarkably, the antioxidant is preferably a hindered phenol-based antioxidant. As the antioxidant, a commercially available product can be used.

[0049] Specific examples of antioxidants include pentaerythritol tetrakis(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate) (manufactured by Ciba Japan, "IRGANOX 1010"), 2,2-thio-diethylenebis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] (manufactured by Ciba Japan, "IRGANOX 1035"), and 1,3,5-tris[[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]methyl]-1,3,5-triazine-2,4,6(1H,3H,5H)-trione (manufactured by Ciba Japan, "IRGANOX 3114").

[0050] -Light stabilizer- Examples of the light stabilizer include hindered amine light stabilizers, phenol light stabilizers, phosphorus light stabilizers, and thioether light stabilizers. Among them, from the viewpoint of obtaining the effects of the present invention remarkably, the light stabilizer is preferably a hindered amine light stabilizer. The light stabilizer may be a commercially available product.

[0051] Specific examples of light stabilizers include ADEKA's LA-52 (butane-1,2,3,4-tetracarboxylic acid tetrakis(1,2,2,6,6-pentamethyl-4-piperidinyl)), LA-57 (1,2,3,4-butanetetracarboxylic acid tetrakis(2,2,6,6-tetramethyl-4-piperidinyl)), LA-63P (mixed ester of 1,2,3,4-butanetetracarboxylic acid with 1,2,2,6,6-pentamethyl-4-piperidinol and 3,9-bis(2-hydroxy-1,1-dimethylethyl)-2,4,8,10-tetraoxaspiro[5.5]undecane), and LA-72 (sebacic acid bis(1,2,2,6,6-pentamethyl-4-piperidyl)).

[0052] -Coloring agent- As the colorant, a pigment may be used, a dye may be used, or a combination of these may be used. Among them, from the viewpoint of obtaining the effects of the present invention significantly, a pigment is preferable as the colorant.

[0053] Examples of the pigment include blue pigments, yellow pigments, red pigments, black pigments, green pigments, etc. (however, white pigments are excluded). Examples of the blue pigment include pigments such as phthalocyanine, anthraquinone, and dioxazine. Examples of the yellow pigment include pigments such as monoazo, disazo, condensed azo, benzimidazolone, isoindolinone, and anthraquinone. Examples of the red pigment include pigments such as monoazo, disazo, azo lake, benzimidazolone, perylene, diketopyrrolopyrrole, condensed azo, anthraquinone, and quinacridone. Examples of the black pigment include carbon black and graphite. Examples of the green pigment include pigments such as phthalocyanine. One or more types of pigments may be used in combination, and one or more types selected from the group consisting of blue pigments, yellow pigments, red pigments, black pigments, and green pigments may be appropriately blended.

[0054] Examples of dyes include azo dyes (monoazo, disazo, etc.), azo-methine dyes, anthraquinone dyes, quinoline dyes, ketone imine dyes, fluorone dyes, nitro dyes, xanthene dyes, acenaphthene dyes, quinophthalone dyes, aminoketone dyes, methine dyes, perylene dyes, coumarin dyes, perinone dyes, triphenyl dyes, triarylmethane dyes, phthalocyanine dyes, isochlorophenol dyes, azine dyes, and mixtures thereof.

[0055] The colorant may be a commercially available product, such as Cyanine Blue 4920 (manufactured by Dainichiseika Chemicals Co., Ltd.), carbon black (manufactured by Mitsubishi Chemical Corporation, Tokai Carbon Co., Ltd., Asahi Carbon Co., Ltd., Shinnichika Carbon Co., Ltd., Nippon Pigment Co., Ltd., Toyo Color Co., Ltd., and Mikuni Shikishoku Co., Ltd.), etc.

[0056] The component (C) may be used alone or in combination of two or more types.

[0057] From the viewpoint of suppressing haloing, the content of the (C) component is preferably 0.01% by mass or more, more preferably 0.1% by mass or more, and even more preferably 0.5% by mass or more, based on 100% by mass of the non-volatile components in the resin composition. The upper limit is preferably 10% by mass or less, more preferably 5% by mass or less, and even more preferably 1.5% by mass or less.

[0058] <(D) Inorganic filler> The resin composition contains (D) an inorganic filler. This makes it possible to obtain a cured product with a low dielectric tangent. An inorganic compound is used as the material for the inorganic filler. Examples of the material for the inorganic filler include silica, alumina, glass, cordierite, silicon oxide, barium sulfate, barium carbonate, talc, clay, mica powder, zinc oxide, hydrotalcite, boehmite, aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, magnesium oxide, boron nitride, aluminum nitride, manganese nitride, aluminum borate, strontium carbonate, strontium titanate, calcium titanate, magnesium titanate, bismuth titanate, titanium oxide, zirconium oxide, barium titanate, barium zirconate titanate, barium zirconate, calcium zirconate, zirconium phosphate, and zirconium tungstate phosphate. Among these, silica is particularly suitable. Examples of silica include amorphous silica, fused silica, crystalline silica, synthetic silica, and hollow silica. In addition, spherical silica is preferable as the silica. The (D) inorganic filler may be used alone or in combination of two or more kinds.

[0059] (D) Commercially available inorganic fillers include, for example, "UFP-30" manufactured by Denka; "SP60-05" and "SP507-05" manufactured by Nippon Steel & Sumitomo Metal Materials Co., Ltd.; "YC100C", "YA050C", "YA050C-MJE", and "YA010C" manufactured by Admatechs Co., Ltd.; "Silfill NSS-3N", "Silfill NSS-4N", and "Silfill NSS-5N" manufactured by Tokuyama Corporation; and "SC2500SQ", "SO-C4", "SO-C2", and "SO-C1" manufactured by Admatechs Co., Ltd.

[0060] From the viewpoint of significantly obtaining the desired effects of the present invention, the average particle size of the (D) inorganic filler is preferably 0.01 μm or more, more preferably 0.05 μm or more, particularly preferably 0.1 μm or more, and is preferably 5 μm or less, more preferably 2 μm or less, and even more preferably 1 μm or less.

[0061] The average particle size of the inorganic filler (D) can be measured by a laser diffraction / scattering method based on the Mie scattering theory. Specifically, the particle size distribution of the inorganic filler is created on a volume basis using a laser diffraction / scattering particle size distribution measuring device, and the median diameter is used as the average particle size. The measurement sample can be prepared by weighing 100 mg of the inorganic filler and 10 g of methyl ethyl ketone into a vial and dispersing the mixture by ultrasonic waves for 10 minutes. The measurement sample is measured using a laser diffraction particle size distribution measuring device with blue and red light wavelengths as the light source, and the volume-based particle size distribution of the inorganic filler (D) is measured using a flow cell method, and the average particle size is calculated from the obtained particle size distribution as the median diameter. An example of a laser diffraction particle size distribution measuring device is the "LA-960" manufactured by Horiba, Ltd.

[0062] The specific surface area of ​​the (D) inorganic filler is preferably 1 m or less from the viewpoint of significantly obtaining the desired effects of the present invention. 2 / g or more, more preferably 2m 2 / g or more, particularly preferably 3m 2 / g or more. There is no particular upper limit, but it is preferably 60m 2 / g or less, 50m 2 / g or less or 40m2 The specific surface area is determined by adsorbing nitrogen gas onto the surface of a sample using a specific surface area measuring device (Macsorb HM-1210 manufactured by Mountec Co., Ltd.) according to the BET method, and calculating the specific surface area using the BET multipoint method.

[0063] (D) The inorganic filler is preferably treated with a surface treatment agent from the viewpoint of improving moisture resistance and dispersibility. Examples of the surface treatment agent include fluorine-containing silane coupling agents, aminosilane coupling agents, epoxysilane coupling agents, mercaptosilane coupling agents, silane coupling agents, alkoxysilanes, organosilazane compounds, titanate coupling agents, etc. The surface treatment agent may be used alone or in any combination of two or more.

[0064] Examples of commercially available surface treatment agents include Shin-Etsu Chemical Co., Ltd.'s "KBM403" (3-glycidoxypropyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBM803" (3-mercaptopropyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBE903" (3-aminopropyltriethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBM573" (N-phenyl-3-aminopropyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "SZ-31" (hexamethyldisilazane), Shin-Etsu Chemical Co., Ltd.'s "KBM103" (phenyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBM-4803" (long-chain epoxy-type silane coupling agent), and Shin-Etsu Chemical Co., Ltd.'s "KBM-7103" (3,3,3-trifluoropropyltrimethoxysilane).

[0065] The degree of surface treatment with the surface treatment agent is preferably within a predetermined range from the viewpoint of improving the dispersibility of the inorganic filler. Specifically, 100 parts by mass of the inorganic filler is preferably surface-treated with 0.2 parts by mass to 5 parts by mass of the surface treatment agent, more preferably 0.2 parts by mass to 3 parts by mass, and even more preferably 0.3 parts by mass to 2 parts by mass.

[0066] The degree of surface treatment with the surface treatment agent can be evaluated by the amount of carbon per unit surface area of ​​the inorganic filler. From the viewpoint of improving the dispersibility of the inorganic filler, the amount of carbon per unit surface area of ​​the inorganic filler is set to 0.02 mg / m 2 More than 0.1 mg / m is preferable. 2 More preferably, 0.2 mg / m or more 2 On the other hand, from the viewpoint of suppressing an increase in the melt viscosity of the resin varnish and the melt viscosity in the form of a sheet, it is more preferable that the content is 1 mg / m 2 Less than 0.8 mg / m is preferred. 2 Less than 0.5 mg / m is more preferable. 2 The following is even more preferred:

[0067] The amount of carbon per unit surface area of ​​the inorganic filler can be measured after the surface-treated inorganic filler is washed with a solvent (e.g., methyl ethyl ketone (MEK)). Specifically, a sufficient amount of MEK as a solvent is added to the inorganic filler that has been surface-treated with a surface treatment agent, and ultrasonic cleaning is performed at 25°C for 5 minutes. After removing the supernatant and drying the solid content, the amount of carbon per unit surface area of ​​the inorganic filler can be measured using a carbon analyzer. The carbon analyzer that can be used is the "EMIA-320V" manufactured by Horiba, Ltd.

[0068] The content of the (D) inorganic filler is preferably 50% by mass or more, more preferably 53% by mass or more, and even more preferably 55% by mass or more, based on 100% by mass of the non-volatile components in the resin composition, from the viewpoint of reducing the dielectric loss tangent. Also, from the viewpoint of maintaining the adhesion, the content is preferably 90% by mass or less, more preferably 85% by mass or less, and even more preferably 80% by mass or less.

[0069] <(E) Hardener> The resin composition may further contain a curing agent (E) as an optional component in addition to the above-mentioned components. The curing agent (E) usually has a function of reacting with the component (A) to cure the resin composition. The curing agent (E) may be used alone or in combination of two or more kinds.

[0070] Examples of the (E) curing agent include active ester-based curing agents, phenol-based curing agents, naphthol-based curing agents, benzoxazine-based curing agents, cyanate ester-based curing agents, carbodiimide-based curing agents, amine-based curing agents, and acid anhydride-based curing agents.

[0071] As the active ester curing agent, a compound having one or more active ester groups in one molecule can be used. Among them, as the active ester curing agent, a compound having two or more highly reactive ester groups in one molecule, such as phenol esters, thiophenol esters, N-hydroxyamine esters, and esters of heterocyclic hydroxy compounds, is preferred. The active ester curing agent is preferably one obtained by a condensation reaction between a carboxylic acid compound and / or a thiocarboxylic acid compound and a hydroxy compound and / or a thiol compound. In particular, from the viewpoint of improving heat resistance, an active ester curing agent obtained from a carboxylic acid compound and a hydroxy compound is preferred, and an active ester curing agent obtained from a carboxylic acid compound and a phenol compound and / or a naphthol compound is more preferred.

[0072] Examples of the carboxylic acid compound include benzoic acid, acetic acid, succinic acid, maleic acid, itaconic acid, phthalic acid, isophthalic acid, terephthalic acid, and pyromellitic acid.

[0073] Examples of phenol compounds or naphthol compounds include hydroquinone, resorcin, bisphenol A, bisphenol F, bisphenol S, phenolphthaline, methylated bisphenol A, methylated bisphenol F, methylated bisphenol S, phenol, o-cresol, m-cresol, p-cresol, catechol, α-naphthol, β-naphthol, 1,5-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 2,6-dihydroxynaphthalene, dihydroxybenzophenone, trihydroxybenzophenone, tetrahydroxybenzophenone, phloroglucin, benzenetriol, dicyclopentadiene-type diphenol compounds, phenol novolac, etc. Here, the term "dicyclopentadiene-type diphenol compounds" refers to diphenol compounds obtained by condensing one molecule of dicyclopentadiene with two molecules of phenol.

[0074] Preferred specific examples of the active ester curing agent include an active ester curing agent containing a dicyclopentadiene-type diphenol structure, an active ester curing agent containing a naphthalene structure, an active ester curing agent containing an acetylated product of phenol novolac, and an active ester curing agent containing a benzoylated product of phenol novolac. Among them, an active ester curing agent containing a naphthalene structure and an active ester curing agent containing a dicyclopentadiene-type diphenol structure are more preferred. The "dicyclopentadiene-type diphenol structure" refers to a divalent structural unit consisting of phenylene-dicyclopentylene-phenylene.

[0075] Commercially available active ester curing agents include "EXB9451", "EXB9460", "EXB9460S", "HPC-8000-65T", "HPC-8000H-65TM", and "EXB-8000L-65TM" (manufactured by DIC Corporation) as active ester curing agents containing a dicyclopentadiene-type diphenol structure; "EXB9416-70BK" and "EXB-8150-65T" (manufactured by DIC Corporation) as active ester curing agents containing a naphthalene structure; and "EXB9416-70BK" and "EXB-8150-65T" (manufactured by DIC Corporation) as active ester curing agents containing an acetylated product of phenol novolac. Examples of such a hardener include "DC808" (manufactured by Mitsubishi Chemical Corporation); "YLH1026" (manufactured by Mitsubishi Chemical Corporation) as an active ester-based hardener containing a benzoyl derivative of phenol novolac; "DC808" (manufactured by Mitsubishi Chemical Corporation) as an active ester-based hardener which is an acetylated derivative of phenol novolac; and "YLH1026" (manufactured by Mitsubishi Chemical Corporation), "YLH1030" (manufactured by Mitsubishi Chemical Corporation), and "YLH1048" (manufactured by Mitsubishi Chemical Corporation) as active ester-based hardeners which are benzoyl derivatives of phenol novolac.

[0076] As the phenol-based curing agent and naphthol-based curing agent, those having a novolak structure are preferred from the viewpoint of heat resistance and water resistance, and from the viewpoint of adhesion to the conductor layer, nitrogen-containing phenol-based curing agents are preferred, and triazine skeleton-containing phenol-based curing agents are more preferred.

[0077] Specific examples of phenol-based curing agents and naphthol-based curing agents include, for example, "MEH-7700", "MEH-7810", and "MEH-7851" manufactured by Meiwa Chemical Industry Co., Ltd.; "NHN", "CBN", and "GPH" manufactured by Nippon Kayaku Co., Ltd.; "SN170", "SN180", "SN190", "SN475", "SN485", "SN495", "SN-495V", and "SN375" manufactured by Nippon Steel & Sumikin Chemical Co., Ltd.; and "TD-2090", "LA-7052", "LA-7054", "LA-1356", "LA-3018-50P", and "EXB-9500" manufactured by DIC Corporation.

[0078] Specific examples of benzoxazine-based curing agents include "JBZ-OD100" (benzoxazine ring equivalent: 218), "JBZ-OP100D" (benzoxazine ring equivalent: 218), and "ODA-BOZ" (benzoxazine ring equivalent: 218) manufactured by JFE Chemical Corporation; "Pd" (benzoxazine ring equivalent: 217) and "Fa" (benzoxazine ring equivalent: 217) manufactured by Shikoku Chemical Industry Co., Ltd.; and "HFB2006M" (benzoxazine ring equivalent: 432) manufactured by Showa Polymer Co., Ltd.

[0079] Examples of cyanate ester curing agents include bifunctional cyanate resins such as bisphenol A dicyanate, polyphenol cyanate, oligo(3-methylene-1,5-phenylene cyanate), 4,4'-methylenebis(2,6-dimethylphenyl cyanate), 4,4'-ethylidene diphenyl dicyanate, hexafluorobisphenol A dicyanate, 2,2-bis(4-cyanate)phenylpropane, 1,1-bis(4-cyanate phenylmethane), bis(4-cyanate-3,5-dimethylphenyl)methane, 1,3-bis(4-cyanate phenyl-1-(methylethylidene))benzene, bis(4-cyanate phenyl)thioether, and bis(4-cyanate phenyl)ether; polyfunctional cyanate resins derived from phenol novolac and cresol novolac; and prepolymers in which these cyanate resins are partially converted to triazine. Specific examples of cyanate ester-based curing agents include "PT30" and "PT60" (phenol novolac type multifunctional cyanate ester resins), "ULL-950S" (multifunctional cyanate ester resin), "BA230", and "BA230S75" (prepolymers in which part or all of bisphenol A dicyanate has been converted to triazine to form a trimer), all of which are manufactured by Lonza Japan.

[0080] Specific examples of carbodiimide-based curing agents include Carbodilite (registered trademark) V-03 (carbodiimide group equivalent: 216, V-05 (carbodiimide group equivalent: 262), V-07 (carbodiimide group equivalent: 200); V-09 (carbodiimide group equivalent: 200), all manufactured by Nisshinbo Chemical Inc.; and Stavaxol (registered trademark) P (carbodiimide group equivalent: 302), all manufactured by Rhein Chemie.

[0081] The amine-based curing agent may be a curing agent having one or more amino groups in one molecule, such as aliphatic amines, polyether amines, alicyclic amines, aromatic amines, etc., and among them, aromatic amines are preferred from the viewpoint of achieving the desired effects of the present invention. The amine-based curing agent is preferably a primary amine or a secondary amine, and more preferably a primary amine. Specific examples of amine-based curing agents include 4,4'-methylenebis(2,6-dimethylaniline), diphenyldiaminosulfone, 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylsulfone, 3,3'-diaminodiphenylsulfone, m-phenylenediamine, m-xylylenediamine, diethyltoluenediamine, 4,4'-diaminodiphenylether, 3,3'-dimethyl-4,4'-diaminobiphenyl, 2,2'-dimethyl-4,4'-diaminobiphenyl, 3,3'-dihydroxybenzidine, 2,2-bis(3-amino-4-hydroxyphenyl)propanediamine, and the like. bis(4-aminophenyl)propane, 3,3-dimethyl-5,5-diethyl-4,4-diphenylmethanediamine, 2,2-bis(4-aminophenyl)propane, 2,2-bis(4-(4-aminophenoxy)phenyl)propane, 1,3-bis(3-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, 4,4'-bis(4-aminophenoxy)biphenyl, bis(4-(4-aminophenoxy)phenyl)sulfone, bis(4-(3-aminophenoxy)phenyl)sulfone, etc. The amine-based curing agent may be a commercially available product, for example, "KAYABOND C-200S", "KAYABOND C-100", "KAYAHARD AA", "KAYAHARD AB", "KAYAHARD AS" manufactured by Nippon Kayaku Co., Ltd., and "Epicure W" manufactured by Mitsubishi Chemical Corporation.

[0082] Examples of the acid anhydride curing agent include a curing agent having one or more acid anhydride groups in one molecule. Specific examples of the acid anhydride curing agent include phthalic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, methylnadic anhydride, hydrogenated methylnadic anhydride, trialkyltetrahydrophthalic anhydride, dodecenyl succinic anhydride, 5-(2,5-dioxotetrahydro-3-furanyl)-3-methyl-3-cyclohexene-1,2-dicarboxylic anhydride, trimellitic anhydride, pyromellitic anhydride, and benzophenonetetracarboxylic dianhydride. Examples of acid anhydrides include anhydrides, biphenyltetracarboxylic dianhydride, naphthalenetetracarboxylic dianhydride, oxydiphthalic dianhydride, 3,3'-4,4'-diphenylsulfonetetracarboxylic dianhydride, 1,3,3a,4,5,9b-hexahydro-5-(tetrahydro-2,5-dioxo-3-furanyl)-naphtho[1,2-C]furan-1,3-dione, ethylene glycol bis(anhydrotrimellitate), and polymeric acid anhydrides such as styrene-maleic acid resin, which is a copolymer of styrene and maleic acid.

[0083] From the viewpoint of obtaining the desired effect of the present invention remarkably, the (E) curing agent is preferably one or more selected from benzoxazine-based curing agents, carbodiimide-based curing agents, phenol-based curing agents, and active ester-based curing agents, and more preferably one or more selected from benzoxazine-based curing agents, carbodiimide-based curing agents, and active ester-based curing agents. Among them, the (E) curing agent preferably contains a benzoxazine-based curing agent or a carbodiimide-based curing agent in addition to the active ester-based curing agent, and more preferably contains a benzoxazine-based curing agent or a carbodiimide-based curing agent in addition to the active ester-based curing agent and the phenol-based curing agent.

[0084] When an active ester curing agent is included as the (E) curing agent, it is preferable to adjust the amount of the (A) component and the active ester curing agent so that the ratio of the amount of the (A) component and the active ester curing agent is within a predetermined range, from the viewpoint of obtaining a cured product with a low dielectric tangent and excellent adhesion. Specifically, the value obtained by dividing the mass of the (A) component by the epoxy equivalent is defined as a1. This value "a1" indicates the equivalent number (eq.) of the epoxy group contained in the (A) component. In addition, the value obtained by dividing the mass of the active ester curing agent by the active ester group equivalent is defined as e1. This value "e1" indicates the equivalent number (eq.) of the active ester group. In this case, e1 / a1 is 0.1 or more, preferably 0.3 or more, more preferably 0.5 or more. The upper limit is preferably 5 or less, more preferably 3 or less, and even more preferably 2 or less. Here, when the resin composition contains two or more kinds of (A) components, the above a1 is the total value obtained by dividing the mass of each epoxy resin present in the resin composition by each epoxy equivalent. When two or more types of active ester curing agents are contained, the above e1 is the total value obtained by dividing the mass of each active ester curing agent present in the resin composition by the active ester group equivalent of each active ester curing agent.

[0085] When a benzoxazine-based curing agent is included as the (E) curing agent, it is preferable to adjust the amount of the (B) component and the benzoxazine-based curing agent so that the ratio of the amount of the (B) component and the benzoxazine-based curing agent is within a predetermined range from the viewpoint of obtaining a cured product with excellent adhesion. Specifically, the value obtained by dividing the mass of the (B) component by the (meth)acryloyl group equivalent of the (B) component is defined as b2. This value "b2" represents the number of equivalents (eq.) of the (meth)acryloyl group equivalent contained in the (B) component. In addition, the value obtained by dividing the mass of the benzoxazine-based curing agent by the benzoxazine ring equivalent is defined as e2. This value "e2" represents the number of equivalents (eq.) of the benzoxazine ring. In this case, e2 / b2 is 0.08 or more, preferably 0.1 or more, and more preferably 0.13 or more. The upper limit is 2.5 or less, preferably 2 or less, more preferably 1 or less, 0.5 or less, or 0.25 or less. When the resin composition contains two or more (B) components, the above b2 is the total of all values ​​obtained by dividing the mass of each (meth)acrylic acid ester present in the resin composition by each (meth)acryloyl group equivalent. When the resin composition contains two or more benzoxazine-based curing agents, the above e2 is the total of all values ​​obtained by dividing the mass of the non-volatile components of each benzoxazine-based curing agent present in the resin composition by each benzoxazine ring equivalent.

[0086] When a carbodiimide-based curing agent is included as the curing agent (E), it is preferable to adjust the amount of the (B) component and the carbodiimide-based curing agent so that the mass ratio of the (B) component and the carbodiimide-based curing agent is within a predetermined range, from the viewpoint of obtaining a cured product with excellent adhesion. Specifically, the content (mass%) of the (B) component in the resin composition is b1, and the content (mass%) of the carbodiimide-based curing agent in the resin composition is e3. In this case, e3 / b1 is 0.1 or more, preferably 0.2 or more, and more preferably 0.25 or more. The upper limit is 1.5 or less, preferably 1.3 or less, and more preferably 1.0 or less.

[0087] The ratio of the amount of the epoxy resin (A) to all the curing agents (E) is preferably in the range of 1:0.01 to 1:5, more preferably 1:0.5 to 1:3, and even more preferably 1:1 to 1:2, in terms of the ratio of [total number of epoxy groups in the epoxy resin (A)] to [total number of reactive groups in the curing agent (E)]. Here, the "number of epoxy groups in the epoxy resin (A)" refers to the total value of all values ​​obtained by dividing the mass of the non-volatile components of the epoxy resin (A) present in the resin composition by the epoxy equivalent. In addition, the "number of active groups in the curing agent (E)" refers to the total value of all values ​​obtained by dividing the mass of the non-volatile components of the curing agent (E) present in the resin composition by the active group equivalent. By setting the ratio of the amount of the epoxy resin (A) to the curing agent (E) within this range, the desired effect of the present invention can be obtained significantly.

[0088] From the viewpoint of significantly obtaining the desired effects of the present invention, the content of the (E) curing agent is preferably 5% by mass or more, more preferably 8% by mass or more, and even more preferably 10% by mass or more, relative to 100% by mass of non-volatile components in the resin composition, and is preferably 35% by mass or less, more preferably 30% by mass or less, and even more preferably 25% by mass or less.

[0089] <(F) Curing accelerator> In addition to the above-mentioned components, the resin composition may further contain (F) a curing accelerator as an optional component.

[0090] Examples of the curing accelerator include phosphorus-based curing accelerators, amine-based curing accelerators, imidazole-based curing accelerators, guanidine-based curing accelerators, and metal-based curing accelerators. Among them, phosphorus-based curing accelerators, amine-based curing accelerators, imidazole-based curing accelerators, and metal-based curing accelerators are preferred, and amine-based curing accelerators, imidazole-based curing accelerators, and metal-based curing accelerators are more preferred. The curing accelerator may be used alone or in combination of two or more types.

[0091] Examples of the phosphorus-based curing accelerator include triphenylphosphine, phosphonium borate compounds, tetraphenylphosphonium tetraphenylborate, n-butylphosphonium tetraphenylborate, tetrabutylphosphonium decanoate, (4-methylphenyl)triphenylphosphonium thiocyanate, tetraphenylphosphonium thiocyanate, butyltriphenylphosphonium thiocyanate, and the like, with triphenylphosphine and tetrabutylphosphonium decanoate being preferred.

[0092] Examples of the amine curing accelerator include trialkylamines such as triethylamine and tributylamine, 4-dimethylaminopyridine, benzyldimethylamine, 2,4,6-tris(dimethylaminomethyl)phenol, and 1,8-diazabicyclo(5,4,0)-undecene, with 4-dimethylaminopyridine and 1,8-diazabicyclo(5,4,0)-undecene being preferred.

[0093] Examples of the imidazole curing accelerator include 2-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, 1-benzyl-2-phenylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazolium trimellitate, 1-cyanoethyl-2-phenylimidazolium trimellitate, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine, 2, 4-Diamino-6-[2'-undecylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine isocyanuric acid adduct, 2-phenylimidazole isocyanuric acid adduct, 2-phenyl-4,5-dihydroxymethylimidazole, 2-furan Examples of the imidazole compounds include imidazole compounds such as 2-ethyl-4-methyl-5-hydroxymethylimidazole, 2,3-dihydro-1H-pyrrolo[1,2-a]benzimidazole, 1-dodecyl-2-methyl-3-benzylimidazolium chloride, 2-methylimidazoline, and 2-phenylimidazoline, as well as adducts of imidazole compounds and epoxy resins. Of these, 2-ethyl-4-methylimidazole and 1-benzyl-2-phenylimidazole are preferred.

[0094] As the imidazole-based curing accelerator, a commercially available product may be used, for example, "P200-H50" manufactured by Mitsubishi Chemical Corporation.

[0095] Examples of the guanidine curing accelerator include dicyandiamide, 1-methylguanidine, 1-ethylguanidine, 1-cyclohexylguanidine, 1-phenylguanidine, 1-(o-tolyl)guanidine, dimethylguanidine, diphenylguanidine, trimethylguanidine, tetramethylguanidine, pentamethylguanidine, 1,5,7-triazabicyclo[4.4.0]dec-5-ene, and 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene. Examples of such biguanide include o-[4.4.0]dec-5-ene, 1-methylbiguanide, 1-ethylbiguanide, 1-n-butylbiguanide, 1-n-octadecylbiguanide, 1,1-dimethylbiguanide, 1,1-diethylbiguanide, 1-cyclohexylbiguanide, 1-allylbiguanide, 1-phenylbiguanide, and 1-(o-tolyl)biguanide. Of these, dicyandiamide and 1,5,7-triazabicyclo[4.4.0]dec-5-ene are preferred.

[0096] Examples of metal-based curing accelerators include organometallic complexes or organometallic salts of metals such as cobalt, copper, zinc, iron, nickel, manganese, and tin. Specific examples of organometallic complexes include organocobalt complexes such as cobalt(II) acetylacetonate and cobalt(III) acetylacetonate, organocopper complexes such as copper(II) acetylacetonate, organozinc complexes such as zinc(II) acetylacetonate, organoiron complexes such as iron(III) acetylacetonate, organonickel complexes such as nickel(II) acetylacetonate, and organomanganese complexes such as manganese(II) acetylacetonate. Examples of organometallic salts include zinc octylate, tin octylate, zinc naphthenate, cobalt naphthenate, tin stearate, and zinc stearate.

[0097] From the viewpoint of significantly obtaining the desired effects of the present invention, the content of the (F) curing accelerator is preferably 0.01 mass% or more, more preferably 0.03 mass% or more, and even more preferably 0.05 mass% or more, and is preferably 0.5 mass% or less, more preferably 0.4 mass% or less, and even more preferably 0.3 mass% or less, based on 100 mass% of non-volatile components in the resin composition.

[0098] <(G) Polymerization initiator> In addition to the above-mentioned components, the resin composition may further contain a polymerization initiator (G) as an optional component. The polymerization initiator (G) usually has a function of promoting crosslinking of the (meth)acryloyl group in the component (B). The polymerization initiator (G) may be used alone or in combination of two or more kinds.

[0099] (G) Examples of polymerization initiators include peroxides such as t-butylcumyl peroxide, t-butyl peroxyacetate, α,α'-di(t-butylperoxy)diisopropylbenzene, t-butyl peroxylaurate, t-butylperoxy-2-ethylhexanoate, t-butylperoxyneodecanoate, and t-butyl peroxybenzoate.

[0100] (G) Commercially available polymerization initiators include, for example, “Percumyl P”, “Percumyl D”, “Perbutyl C”, “Perbutyl A”, “Perbutyl P”, “Perbutyl L”, “Perbutyl O”, “Perbutyl ND”, and “Perbutyl Z” manufactured by NOF Corporation.

[0101] From the viewpoint of significantly obtaining the desired effects of the present invention, the content of the (G) polymerization initiator is preferably 0.01 mass% or more, more preferably 0.02 mass% or more, and even more preferably 0.03 mass% or more, based on 100 mass% of non-volatile components in the resin composition, and is preferably 0.5 mass% or less, more preferably 0.3 mass% or less, and even more preferably 0.1 mass% or less.

[0102] <(H)Thermoplastic resin> In addition to the above-mentioned components, the resin composition may further contain (H) a thermoplastic resin as an optional component.

[0103] Examples of the thermoplastic resin as component (H) include phenoxy resin, polyvinyl acetal resin, polyolefin resin, polybutadiene resin, polyimide resin, polyamideimide resin, polyetherimide resin, polysulfone resin, polyethersulfone resin, polyphenylene ether resin, polycarbonate resin, polyetheretherketone resin, polyester resin, etc. Among them, phenoxy resin is preferred from the viewpoint of obtaining the desired effect of the present invention remarkably and from the viewpoint of obtaining an insulating layer having small surface roughness and particularly excellent adhesion to the conductor layer. Moreover, the thermoplastic resin may be used alone or in combination of two or more kinds.

[0104] Examples of the phenoxy resin include phenoxy resins having one or more skeletons selected from the group consisting of bisphenol A skeleton, bisphenol F skeleton, bisphenol S skeleton, bisphenolacetophenone skeleton, novolac skeleton, biphenyl skeleton, fluorene skeleton, dicyclopentadiene skeleton, norbornene skeleton, naphthalene skeleton, anthracene skeleton, adamantane skeleton, terpene skeleton, and trimethylcyclohexane skeleton. The terminal of the phenoxy resin may be any functional group such as a phenolic hydroxyl group or an epoxy group.

[0105] Specific examples of phenoxy resins include "1256" and "4250" manufactured by Mitsubishi Chemical Corporation (both of which are phenoxy resins containing a bisphenol A skeleton); "YX8100" manufactured by Mitsubishi Chemical Corporation (phenoxy resin containing a bisphenol S skeleton); "YX6954" manufactured by Mitsubishi Chemical Corporation (phenoxy resin containing a bisphenol acetophenone skeleton); "FX280" and "FX293" manufactured by Nippon Steel & Sumikin Chemical Co., Ltd.; "YL7500BH30", "YX6954BH30", "YX7553", "YX7553BH30", "YL7769BH30", "YL6794", "YL7213", "YL7290", and "YL7482" manufactured by Mitsubishi Chemical Corporation.

[0106] Examples of polyvinyl acetal resins include polyvinyl formal resins and polyvinyl butyral resins, and polyvinyl butyral resins are preferred. Specific examples of polyvinyl acetal resins include S-LEC BH series, BX series (e.g., BX-5Z), KS series (e.g., KS-1), BL series, and BM series manufactured by Sekisui Chemical Co., Ltd.

[0107] Specific examples of polyimide resins include "Rikacoat SN20" and "Rikacoat PN20" manufactured by New Japan Chemical Co., Ltd. Specific examples of polyimide resins also include modified polyimides such as linear polyimides obtained by reacting bifunctional hydroxyl-terminated polybutadiene, a diisocyanate compound, and a tetrabasic acid anhydride (polyimides described in JP-A-2006-37083), and polysiloxane skeleton-containing polyimides (polyimides described in JP-A-2002-12667 and JP-A-2000-319386, etc.).

[0108] Specific examples of polyamide-imide resins include "Viromax HR11NN" and "Viromax HR16NN" manufactured by Toyobo Co., Ltd. Specific examples of polyamide-imide resins also include modified polyamide-imides such as "KS9100" and "KS9300" (polysiloxane skeleton-containing polyamide-imide) manufactured by Hitachi Chemical Co., Ltd.

[0109] A specific example of the polyethersulfone resin is "PES5003P" manufactured by Sumitomo Chemical Co., Ltd.

[0110] A specific example of the polyphenylene ether resin is the oligophenylene ether-styrene resin "OPE-2St 1200" manufactured by Mitsubishi Gas Chemical Company.

[0111] Specific examples of polysulfone resins include polysulfones "P1700" and "P3500" manufactured by Solvay Advanced Polymers.

[0112] From the viewpoint of significantly obtaining the desired effects of the present invention, the weight average molecular weight (Mw) of the thermoplastic resin (H) is preferably 8,000 or more, more preferably 10,000 or more, and particularly preferably 20,000 or more, and is preferably 70,000 or less, more preferably 60,000 or less, and particularly preferably 50,000 or less.

[0113] From the viewpoint of significantly obtaining the desired effects of the present invention, the content of the (H) thermoplastic resin, relative to 100 mass% of the non-volatile components in the resin composition, is preferably 0.1 mass% or more, more preferably 0.2 mass% or more, even more preferably 0.3 mass% or more, and is preferably 5 mass% or less, more preferably 3 mass% or less, even more preferably 1 mass% or less.

[0114] <(I) Flame retardants> The resin composition may contain (I) a flame retardant as an optional component. (I) Flame retardants include, for example, phosphazene compounds, organic phosphorus-based flame retardants, organic nitrogen-containing phosphorus compounds, nitrogen compounds, silicone-based flame retardants, metal hydroxides, etc., and phosphazene compounds are preferred. Flame retardants may be used alone or in combination of two or more.

[0115] The phosphazene compound is a cyclic compound having nitrogen and phosphorus as constituent elements, and is preferably a phosphazene compound having a phenolic hydroxyl group.Specific examples of the phosphazene compound include "SPH-100", "SPS-100", "SPB-100", and "SPE-100" manufactured by Otsuka Chemical Co., Ltd., and "FP-100", "FP-110", "FP-300", and "FP-400" manufactured by Fushimi Pharmaceutical Co., Ltd.

[0116] As the flame retardant other than the phosphazene compound, a commercially available product may be used, for example, "HCA-HQ" manufactured by Sankosha Co., Ltd., and "PX-200" manufactured by Daihachi Chemical Industry Co., Ltd. As the flame retardant, one that is not easily hydrolyzed is preferable, for example, 10-(2,5-dihydroxyphenyl)-10-hydro-9-oxa-10-phosphaphenanthrene-10-oxide, etc. is preferable.

[0117] When the resin composition contains the flame retardant (I), the amount of the flame retardant (I) is preferably 0.1% by mass or more, more preferably 0.2% by mass or more, and even more preferably 0.3% by mass or more, based on 100% by mass of the non-volatile components in the resin composition, from the viewpoint of significantly obtaining the desired effects of the present invention. The upper limit is preferably 3% by mass or less, more preferably 2% by mass or less, and even more preferably 1% by mass or less.

[0118] <(J) Other Additives> The resin composition may further contain other additives as optional components in addition to the above-mentioned components. Examples of such additives include resin additives such as organometallic compounds such as organocopper compounds, organozinc compounds, and organocobalt compounds; thickeners; defoamers; leveling agents; adhesion promoters; and colorants. These additives may be used alone or in combination of two or more at any ratio.

[0119] <Characteristics of resin composition> By curing the resin composition of the present invention, an insulating layer formed of a cured product of the resin composition can be obtained. When a via hole is formed in this insulating layer and a roughening treatment is performed, the haloing phenomenon can be suppressed. These effects will be described below with reference to the drawings.

[0120] 1 is a cross-sectional view showing an insulating layer 100 obtained by curing the resin composition of the present invention into a sheet shape, together with an inner layer substrate 200. This Fig. 1 shows a cross section of the insulating layer 100 cut along a plane that passes through the center 120C of the bottom 120 of the via hole 110 and is parallel to the thickness direction of the insulating layer 100.

[0121] As shown in FIG. 1, the insulating layer 100 is a layer obtained by curing a resin composition formed on an inner layer substrate 200 including a conductor layer 210, and is made of a cured product of the resin composition. In addition, a via hole 110 is formed in the insulating layer 100. The via hole 110 is generally formed in a forward tapered shape in which the diameter is larger toward the surface 100U of the insulating layer 100 opposite the conductor layer 210 and the diameter is smaller toward the conductor layer 210, and is ideally formed in a columnar shape having a constant diameter in the thickness direction of the insulating layer 100. This via hole 110 is usually formed by irradiating the surface 100U of the insulating layer 100 opposite the conductor layer 210 with laser light to remove a part of the insulating layer 100.

[0122] The bottom of the via hole 110 on the conductor layer 210 side is appropriately called "via bottom" and indicated by the reference symbol 120. The diameter of the via bottom 120 is called bottom diameter Lb. The opening formed on the opposite side of the via hole 110 from the conductor layer 210 is appropriately called "via top" and indicated by the reference symbol 130. The diameter of the via top 130 is called top diameter Lt. Usually, the via bottom 120 and the via top 130 are formed so that their planar shape is circular when viewed from the thickness direction of the insulating layer 100, but they may be elliptical. When the planar shape of the via bottom 120 and the via top 130 is elliptical, the bottom diameter Lb and the top diameter Lt respectively represent the major axis of the elliptical shape.

[0123] In this case, the closer to 100% the taper ratio Lb / Lt, obtained by dividing the bottom diameter Lb by the top diameter Lt, the better the shape of the via hole 110. By using the resin composition of the present invention, it is usually possible to easily control the shape of the via hole 110, so that a via hole 110 with a taper ratio Lb / Lt close to 100% can be realized.

[0124] The taper ratio Lb / Lt of the via hole 110 can be calculated from the bottom diameter Lb and the top diameter Lt of the via hole 110. The bottom diameter Lb and the top diameter Lt of the via hole 110 can be measured by cutting out the insulating layer 100 using a FIB (focused ion beam) so as to reveal a cross section that is parallel to the thickness direction of the insulating layer 100 and passes through the center 120C of the via bottom 120, and then observing the cross section with an electron microscope.

[0125] FIG. 2 is a plan view that typically shows a surface 100U of insulating layer 100 obtained by curing the resin composition of the present invention, the surface being opposite to conductive layer 210 (not shown in FIG. 2).

[0126] 2, when the insulating layer 100 having the via hole 110 formed therein is observed, a discolored portion 140 may be observed around the via hole 110, where the insulating layer 100 has discolored from an edge 180 of the via top 130 to an edge 190 on the outer periphery of the discolored portion 140. The discolored portion 140 may be formed by deterioration of the resin during the formation of the via hole 110, and is usually formed continuously from the via hole 110. In many cases, the discolored portion 140 is a whitened portion.

[0127] 3 is a cross-sectional view showing a roughening-treated insulating layer 100 obtained by curing the resin composition of the present invention, together with an inner layer substrate 200. In FIG. 3, a cross section of the insulating layer 100 is shown cut along a plane passing through a center 120C of a via bottom 120 of a via hole 110 and parallel to the thickness direction of the insulating layer 100. As shown in FIG. 3, when a roughening treatment is performed on an insulating layer 100 in which a via hole 110 is formed, a haloing phenomenon may occur, causing the insulating layer 100 in the discolored portion 140 to peel off from the conductor layer 210, and forming a gap portion 160 that continues from the edge 150 of the via bottom 120.

[0128] By using the resin composition of the present invention, the above-mentioned haloing phenomenon can be suppressed, and therefore, peeling of the insulating layer 100 from the conductor layer 210 can be suppressed, so that the size of the gap 160 can be reduced.

[0129] The edge 150 of the via bottom 120 corresponds to the edge on the inner circumference side of the gap 160. Therefore, the distance Wb from the edge 150 of the via bottom 120 to the end 170 on the outer circumference side of the gap 160 (i.e., the end farther from the center 120C of the via bottom 120) corresponds to the size of the gap 160 in the in-plane direction. Here, the in-plane direction refers to the direction perpendicular to the thickness direction of the insulating layer 100. In the following description, the distance Wb may be referred to as the halo distance Wb of the via hole 110 from the edge 150 of the via bottom 120. The degree of suppression of the halo phenomenon can be evaluated by the halo distance Wb from the edge 150 of the via bottom 120. Specifically, it can be evaluated that the halo distance Wb from the edge 150 of the via bottom 120 is smaller, the more effectively the halo phenomenon can be suppressed.

[0130] For example, a resin composition layer containing a resin composition formed on a copper foil is heated at 130°C for 30 minutes, then heated at 170°C for 30 minutes to harden the insulating layer 100, and a CO2 laser beam is irradiated to form a via hole 110 with a top diameter Lt of about 50 μm or about 30 μm. The insulating layer 100 is then immersed in a swelling liquid at 60°C for 10 minutes, then immersed in an oxidizing agent solution at 80°C for 20 minutes, then immersed in a neutralizing liquid at 40°C for 5 minutes, and then dried at 80°C for 30 minutes. By using the resin composition of the present invention, the halo distance Wb from the edge 150 of the via bottom 120 of the via hole 110 of the insulating layer 100 thus obtained can be preferably 10 μm or less, more preferably 5 μm or less, even more preferably 4.5 μm or less, and particularly preferably 4 μm or less.

[0131] The irradiation conditions of the CO2 laser light are as follows: when the top diameter Lt is about 50 μm, the mask diameter is 1.60 mm, the focus offset value is 0.050, the pulse width is 25 μs, the power is 0.66 W, the aperture is 13, the number of shots is 2, and the burst mode (10 kHz). Furthermore, when the top diameter Lt is about 30 μm, the mask diameter is 1 mm, the pulse width is 16 μs, the energy is 0.2 mJ / shot, the number of shots is 2, and the burst mode (10 kHz) is set.

[0132] The halo distance Wb from the edge 150 of the via bottom 120 can be measured by using a FIB (focused ion beam) to remove the insulating layer 100 so as to reveal a cross section that is parallel to the thickness direction of the insulating layer 100 and passes through the center 120C of the via bottom 120, and then observing the cross section with an electron microscope.

[0133] Furthermore, by using the resin composition of the present invention, the shape of the via hole 110 in the insulating layer 100 before the roughening treatment can be easily controlled, and therefore, it is usually possible to easily control the shape of the via hole 110 in the insulating layer 100 after the roughening treatment. Therefore, even after the roughening treatment, the shape of the via hole 110 can be made good, just like before the roughening treatment. Therefore, by using the resin composition of the present invention, it is possible to realize a via hole 110 with a taper ratio Lb / Lt close to 100% in the insulating layer after the roughening treatment.

[0134] For example, the resin composition is heated at 130°C for 30 minutes, then heated at 170°C for 30 minutes to harden the insulating layer 100, and then irradiated with CO2 laser light to form a via hole 110 with a top diameter Lt of about 50 μm or about 30 μm. The insulating layer 100 is then immersed in a swelling liquid at 60°C for 10 minutes, then immersed in an oxidizing agent solution at 80°C for 20 minutes, then immersed in a neutralizing liquid at 40°C for 5 minutes, and then dried at 80°C for 30 minutes. In these cases, the taper ratio Lb / Lt of the via hole 110 can be preferably 70% to 100%, more preferably 75% to 100%, and particularly preferably 80% to 100%.

[0135] The irradiation conditions of the CO2 laser light are as follows: when the top diameter Lt is about 40 μm, the mask diameter is 1.60 mm, the focus offset value is 0.050, the pulse width is 25 μs, the power is 0.66 W, the aperture is 13, the number of shots is 2, and the burst mode (10 kHz). Also, when the top diameter Lt is about 10 μm, the mask diameter is 1 mm, the pulse width is 16 μs, the energy is 0.2 mJ / shot, the number of shots is 2, and the burst mode (10 kHz) is set.

[0136] The taper ratio Lb / Lt of the via hole 110 after the roughening treatment can be calculated from the bottom diameter Lb and the top diameter Lt of the via hole 110. The bottom diameter Lb and the top diameter Lt of the via hole 110 can be measured by cutting out the insulating layer 100 using a FIB (focused ion beam) so as to reveal a cross section that is parallel to the thickness direction of the insulating layer 100 and passes through the center 120C of the via bottom 120, and then observing the cross section with an electron microscope.

[0137] Furthermore, according to the study of the present inventor, it has been found that the larger the diameter of the via hole, the larger the size of the gap 160 tends to be. Therefore, the degree of suppression of the halo phenomenon can be evaluated by the ratio of the size of the gap 160 to the diameter of the via hole 110. For example, the evaluation can be performed by the halo ratio Hb to the bottom radius Lb / 2 of the via hole 110. Here, the bottom radius Lb / 2 of the via hole 110 refers to the radius of the via bottom 120 of the via hole 110. Also, the halo ratio Hb to the bottom radius Lb / 2 of the via hole 110 is a ratio obtained by dividing the halo distance Wb from the edge 150 of the via bottom 120 by the bottom radius Lb / 2 of the via hole 110. The smaller the halo ratio Hb to the bottom radius Lb / 2 of the via hole 110, the more effectively the halo phenomenon can be suppressed.

[0138] For example, the insulating layer 100 obtained by heating the resin composition formed on the copper foil at 130°C for 30 minutes, then heating it at 170°C for 30 minutes to harden it is irradiated with CO2 laser light to form a via hole 110 with a top diameter Lt of about 50 μm or about 30 μm. Then, it is immersed in a swelling liquid at 60°C for 10 minutes, then immersed in an oxidizing agent solution at 80°C for 20 minutes, then immersed in a neutralizing liquid at 40°C for 5 minutes, and then dried at 80°C for 30 minutes. The haloing ratio Hb of the via hole 110 formed in the insulating layer 100 thus obtained to the bottom radius Lb / 2 can be preferably 35% or less, more preferably 30% or less, and even more preferably 25% or less.

[0139] The irradiation conditions of the CO2 laser light are as follows: when the top diameter Lt is about 50 μm, the mask diameter is 1.60 mm, the focus offset value is 0.050, the pulse width is 25 μs, the power is 0.66 W, the aperture is 13, the number of shots is 2, and the burst mode (10 kHz). Furthermore, when the top diameter Lt is about 30 μm, the mask diameter is 1 mm, the pulse width is 16 μs, the energy is 0.2 mJ / shot, the number of shots is 2, and the burst mode (10 kHz) is set.

[0140] The halo ratio Hb of the via hole 110 to the bottom radius Lb / 2 can be calculated from the bottom diameter Lb of the via hole 110 and the halo distance Wb from the edge 150 of the via bottom 120 of the via hole 110.

[0141] In the manufacturing process of the printed wiring board, the via hole 110 is usually formed without another conductor layer (not shown) being provided on the surface 100U of the insulating layer 100 opposite the conductor layer 210. Therefore, if the manufacturing process of the printed wiring board is understood, it is possible to clearly recognize the structure in which the via bottom 120 is on the conductor layer 210 side and the via top 130 is open on the opposite side of the conductor layer 210. However, in the completed printed wiring board, there may be cases where conductor layers are provided on both sides of the insulating layer 100. In this case, it may be difficult to distinguish the via bottom 120 and the via top 130 depending on the positional relationship with the conductor layer. However, usually, the top diameter Lt of the via top 130 is equal to or larger than the bottom diameter Lb of the via bottom 120. Therefore, in the above case, it is possible to distinguish the via bottom 120 and the via top 130 depending on the diameter size.

[0142] The resin composition of the present invention not only suppresses the haloing phenomenon, but also provides an insulating layer having a low dielectric tangent and usually excellent adhesion to a conductor layer.

[0143] The cured product obtained by thermally curing the resin composition at 200°C for 90 minutes exhibits the characteristic of having a low dielectric loss tangent. Thus, the cured product provides an insulating layer with a low dielectric loss tangent. The dielectric loss tangent is preferably 0.006 or less, more preferably 0.0055 or less, and even more preferably 0.0053 or less. On the other hand, the lower limit of the dielectric loss tangent is not particularly limited, but may be 0.0001 or more. The dielectric loss tangent can be evaluated according to the method described in the examples below.

[0144] A cured product obtained by thermally curing a resin composition at 130°C for 30 minutes and then at 170°C for 30 minutes usually exhibits a property of excellent adhesion (peel strength) with a plated conductor layer. Thus, the cured product provides an insulating layer with excellent adhesion with a plated conductor layer. The peel strength with the plated conductor layer is preferably 0.3 kgf / cm or more, more preferably 0.35 kgf / cm or more, and even more preferably 0.4 kgf / cm or more. On the other hand, the upper limit of the peel strength is not particularly limited, but may be 5 kgf / cm or less. The peel strength with the plated conductor layer can be evaluated according to the method described in the examples below.

[0145] The resin composition of the present invention has a low dielectric tangent, can suppress the haloing phenomenon, and can usually provide an insulating layer with excellent adhesion to a conductor layer. Therefore, the resin composition of the present invention can be suitably used as a resin composition for insulation purposes. Specifically, it can be suitably used as a resin composition for forming an insulating layer (resin composition for forming an insulating layer) for forming a conductor layer (including a rewiring layer) formed on an insulating layer.

[0146] Furthermore, in the multilayer printed wiring board described below, the resin composition can be suitably used as a resin composition for forming an insulating layer of a multilayer printed wiring board (resin composition for forming an insulating layer of a multilayer printed wiring board) and a resin composition for forming an interlayer insulating layer of a printed wiring board (resin composition for forming an interlayer insulating layer of a printed wiring board).

[0147] In addition, for example, when a semiconductor chip package is manufactured through the following steps (1) to (6), the resin composition of the present invention can be suitably used as a resin composition for a rewiring formation layer (resin composition for forming a rewiring formation layer) as an insulating layer for forming a rewiring layer, and as a resin composition for sealing a semiconductor chip (resin composition for sealing a semiconductor chip). When a semiconductor chip package is manufactured, a rewiring layer may be further formed on the sealing layer. (1) A step of laminating a temporary fixing film onto a substrate; (2) a step of temporarily fixing a semiconductor chip on a temporary fixing film; (3) forming an encapsulation layer on the semiconductor chip; (4) peeling the substrate and the temporary fixing film from the semiconductor chip; (5) forming a rewiring formation layer as an insulating layer on the surface of the semiconductor chip from which the base material and the temporary fixing film have been peeled off; and (6) A step of forming a rewiring layer as a conductor layer on the rewiring formation layer.

[0148] Furthermore, the resin composition of the present invention provides an insulating layer with good component embedding properties, and therefore can be suitably used when the printed wiring board is a circuit board with built-in components.

[0149] [Resin sheet] The resin sheet of the present invention includes a support and a resin composition layer formed from the resin composition of the present invention provided on the support.

[0150] The thickness of the resin composition layer is preferably 50 μm or less, more preferably 40 μm or less, and even more preferably 30 μm or less, from the viewpoint of making the printed wiring board thinner and being able to provide a cured product with excellent insulation even if the cured product of the resin composition is a thin film. The lower limit of the thickness of the resin composition layer is not particularly limited, but can usually be 3 μm or more.

[0151] Examples of the support include films made of plastic materials, metal foils, and release papers, with films made of plastic materials and metal foils being preferred.

[0152] When a film made of a plastic material is used as the support, examples of the plastic material include polyesters such as polyethylene terephthalate (hereinafter sometimes abbreviated as "PET") and polyethylene naphthalate (hereinafter sometimes abbreviated as "PEN"), polycarbonate (hereinafter sometimes abbreviated as "PC"), acrylics such as polymethyl methacrylate (PMMA), cyclic polyolefins, triacetyl cellulose (TAC), polyether sulfide (PES), polyether ketone, polyimide, etc. Among these, polyethylene terephthalate and polyethylene naphthalate are preferred, and inexpensive polyethylene terephthalate is particularly preferred.

[0153] When a metal foil is used as the support, examples of the metal foil include copper foil, aluminum foil, etc., and copper foil is preferred. As the copper foil, a foil made of a single metal, copper, or an alloy of copper and another metal (e.g., tin, chromium, silver, magnesium, nickel, zirconium, silicon, titanium, etc.) may be used.

[0154] The surface of the support to be bonded to the resin composition layer may be subjected to a matte treatment, a corona treatment, or an antistatic treatment.

[0155] In addition, as the support, a support with a release layer having a release layer on the surface to be bonded to the resin composition layer may be used. The release agent used in the release layer of the support with a release layer may be, for example, one or more release agents selected from the group consisting of alkyd resins, polyolefin resins, urethane resins, and silicone resins. The support with a release layer may be a commercially available product, for example, "SK-1", "AL-5", and "AL-7" manufactured by Lintec Corporation, "Lumirror T60" manufactured by Toray Industries, Inc., "Purex" manufactured by Teijin Limited, and "Unipeel" manufactured by Unitika Limited, which are PET films having a release layer mainly composed of an alkyd resin-based release agent.

[0156] The thickness of the support is not particularly limited, but is preferably in the range of 5 μm to 75 μm, and more preferably in the range of 10 μm to 60 μm. When a support with a release layer is used, it is preferable that the total thickness of the support with a release layer is in the above range.

[0157] In one embodiment, the resin sheet may further include other layers as necessary. Examples of such other layers include a protective film equivalent to the support provided on the surface of the resin composition layer that is not bonded to the support (i.e., the surface opposite to the support). The thickness of the protective film is not particularly limited, but is, for example, 1 μm to 40 μm. By laminating the protective film, adhesion of dirt and the like to the surface of the resin composition layer and scratches can be suppressed.

[0158] The resin sheet can be produced, for example, by preparing a resin varnish by dissolving a resin composition in an organic solvent, applying this resin varnish onto a support using a die coater or the like, and then drying the same to form a resin composition layer.

[0159] Examples of organic solvents include ketones such as acetone, methyl ethyl ketone (MEK), and cyclohexanone; acetates such as ethyl acetate, butyl acetate, cellosolve acetate, propylene glycol monomethyl ether acetate, and carbitol acetate; carbitols such as cellosolve and butyl carbitol; aromatic hydrocarbons such as toluene and xylene; and amide solvents such as dimethylformamide, dimethylacetamide (DMAc), and N-methylpyrrolidone. The organic solvents may be used alone or in combination of two or more.

[0160] Drying may be performed by a known method such as heating or hot air blowing. Drying conditions are not particularly limited, but drying is performed so that the content of organic solvent in the resin composition layer becomes 10 mass % or less, preferably 5 mass % or less. Although it varies depending on the boiling point of the organic solvent in the resin varnish, for example, when a resin varnish containing 30 mass % to 60 mass % of organic solvent is used, the resin composition layer can be formed by drying at 50°C to 150°C for 3 minutes to 10 minutes.

[0161] The resin sheet can be stored in a rolled state. When the resin sheet has a protective film, it can be used by peeling off the protective film.

[0162] [Printed wiring board] The printed wiring board of the present invention includes an insulating layer formed from a cured product of the resin composition of the present invention.

[0163] The printed wiring board can be produced, for example, by using the above-mentioned resin sheet by a method including the following steps (I) and (II). (I) A step of laminating a resin sheet on an inner layer substrate so that a resin composition layer of the resin sheet is bonded to the inner layer substrate. (II) A step of thermally curing the resin composition layer to form an insulating layer

[0164] The "inner layer substrate" used in step (I) is a member that becomes the substrate of a printed wiring board, and examples thereof include a glass epoxy substrate, a metal substrate, a polyester substrate, a polyimide substrate, a BT resin substrate, and a thermosetting polyphenylene ether substrate. The substrate may have a conductor layer on one or both sides, and the conductor layer may be patterned. An inner layer substrate having a conductor layer (circuit) formed on one or both sides of the substrate may be called an "inner layer circuit substrate". In addition, an intermediate product on which an insulating layer and / or a conductor layer is to be further formed during the manufacture of a printed wiring board is also included in the "inner layer substrate" of the present invention. When the printed wiring board is a circuit board with built-in components, an inner layer substrate with built-in components may be used.

[0165] The lamination of the inner layer substrate and the resin sheet can be carried out, for example, by thermocompression bonding the resin sheet to the inner layer substrate from the support side. Examples of the member for thermocompression bonding the resin sheet to the inner layer substrate (hereinafter also referred to as the "thermocompression bonding member") include a heated metal plate (such as a SUS plate) or a metal roll (SUS roll). It is preferable to press the thermocompression member not directly onto the resin sheet, but via an elastic material such as heat-resistant rubber so that the resin sheet can sufficiently follow the surface irregularities of the inner layer substrate.

[0166] The lamination of the inner layer substrate and the resin sheet may be performed by a vacuum lamination method. In the vacuum lamination method, the thermocompression temperature is preferably in the range of 60°C to 160°C, more preferably in the range of 80°C to 140°C, the thermocompression pressure is preferably in the range of 0.098MPa to 1.77MPa, more preferably in the range of 0.29MPa to 1.47MPa, and the thermocompression time is preferably in the range of 20 seconds to 400 seconds, more preferably in the range of 30 seconds to 300 seconds. The lamination is preferably performed under reduced pressure conditions of 26.7hPa or less.

[0167] The lamination can be performed by a commercially available vacuum laminator, such as a vacuum pressure laminator manufactured by Meiki Seisakusho Co., Ltd., a vacuum applicator manufactured by Nikko Materials Co., Ltd., or a batch type vacuum pressure laminator.

[0168] After lamination, the laminated resin sheet may be smoothed under normal pressure (atmospheric pressure), for example, by pressing a thermocompression member from the support side. The pressing conditions for the smoothing treatment may be the same as the thermocompression conditions for the lamination. The smoothing treatment may be performed using a commercially available laminator. The lamination and smoothing treatment may be performed consecutively using the commercially available vacuum laminator.

[0169] The support may be removed between step (I) and step (II) or after step (II).

[0170] In step (II), the resin composition layer is thermally cured to form an insulating layer. The conditions for thermally curing the resin composition layer are not particularly limited, and conditions that are usually employed when forming an insulating layer for a printed wiring board may be used.

[0171] For example, the thermal curing conditions for the resin composition layer vary depending on the type of resin composition, etc., but the curing temperature is preferably 120° C. to 240° C., more preferably 150° C. to 220° C., and even more preferably 170° C. to 210° C. The curing time is preferably 5 minutes to 120 minutes, more preferably 10 minutes to 100 minutes, and even more preferably 15 minutes to 100 minutes.

[0172] Before the resin composition layer is thermally cured, the resin composition layer may be preheated at a temperature lower than the curing temperature. For example, prior to thermally curing the resin composition layer, the resin composition layer may be preheated at a temperature of 50° C. or more and less than 120° C. (preferably 60° C. or more and 115° C. or less, more preferably 70° C. or more and 110° C. or less) for 5 minutes or more (preferably 5 minutes to 150 minutes, more preferably 15 minutes to 120 minutes, and even more preferably 15 minutes to 100 minutes).

[0173] In manufacturing a printed wiring board, the steps of (III) drilling holes in the insulating layer, (IV) roughening the insulating layer, and (V) forming a conductor layer may be further carried out. These steps (III) to (V) may be carried out according to various methods known to those skilled in the art for use in manufacturing printed wiring boards. When the support is removed after step (II), the removal of the support may be carried out between steps (II) and (III), between steps (III) and (IV), or between steps (IV) and (V). In addition, the formation of the insulating layer and the conductor layer in steps (II) to (V) may be repeated to form a multilayer wiring board, as necessary.

[0174] Step (III) is a step of drilling holes in the insulating layer, which allows holes such as via holes and through holes to be formed in the insulating layer. Step (III) may be performed using, for example, a drill, a laser, plasma, etc., depending on the composition of the resin composition used to form the insulating layer. The dimensions and shape of the holes may be appropriately determined depending on the design of the printed wiring board.

[0175] Step (IV) is a step of roughening the insulating layer. Usually, in this step (IV), smears are also removed. The procedure and conditions of the roughening treatment are not particularly limited, and known procedures and conditions that are usually used when forming an insulating layer of a printed wiring board can be adopted. For example, the insulating layer can be roughened by performing a swelling treatment with a swelling liquid, a roughening treatment with an oxidizing agent, and a neutralization treatment with a neutralizing liquid in this order. The swelling liquid used in the roughening treatment is not particularly limited, but examples thereof include an alkaline solution, a surfactant solution, and the like, and is preferably an alkaline solution, and as the alkaline solution, a sodium hydroxide solution and a potassium hydroxide solution are more preferable. Examples of commercially available swelling liquids include "Swelling Dip Securigans P" and "Swelling Dip Securigans SBU" manufactured by Atotech Japan. The swelling treatment with a swelling liquid is not particularly limited, but can be performed, for example, by immersing the insulating layer in a swelling liquid at 30°C to 90°C for 1 minute to 20 minutes. From the viewpoint of suppressing the swelling of the resin of the insulating layer to an appropriate level, it is preferable to immerse the insulating layer in a swelling liquid at 40°C to 80°C for 5 to 15 minutes. The oxidizing agent used in the roughening treatment is not particularly limited, but for example, an alkaline permanganate solution in which potassium permanganate or sodium permanganate is dissolved in an aqueous solution of sodium hydroxide can be mentioned. The roughening treatment using an oxidizing agent such as an alkaline permanganate solution is preferably performed by immersing the insulating layer in an oxidizing agent solution heated to 60°C to 100°C for 10 to 30 minutes. In addition, the concentration of the permanganate in the alkaline permanganate solution is preferably 5% by mass to 10% by mass. Examples of commercially available oxidizing agents include alkaline permanganate solutions such as "Concentrate Compact CP" and "Dosing Solution Securigans P" manufactured by Atotech Japan. The neutralizing solution used in the roughening treatment is preferably an acidic aqueous solution, and a commercially available product is, for example, "Reduction Solution Securigant P" manufactured by Atotech Japan Co., Ltd. Treatment with the neutralizing solution can be carried out by immersing the surface that has been roughened with an oxidizing agent in the neutralizing solution at 30°C to 80°C for 1 minute to 30 minutes.From the viewpoint of workability etc., a method in which the object that has been subjected to roughening treatment with an oxidizing agent is immersed in a neutralizing solution at 40° C. to 70° C. for 5 minutes to 20 minutes is preferred.

[0176] In one embodiment, the arithmetic mean roughness (Ra) of the insulating layer surface after the roughening treatment is preferably 120 nm or less, more preferably 110 nm or less, and even more preferably 100 nm or less. The lower limit is not particularly limited, but is preferably 30 nm or more, more preferably 40 nm or more, and even more preferably 50 nm or more. The arithmetic mean roughness (Ra) of the insulating layer surface can be measured using a non-contact surface roughness meter.

[0177] Step (V) is a step of forming a conductor layer, and the conductor layer is formed on the insulating layer. The conductor material used for the conductor layer is not particularly limited. In a preferred embodiment, the conductor layer contains one or more metals selected from the group consisting of gold, platinum, palladium, silver, copper, aluminum, cobalt, chromium, zinc, nickel, titanium, tungsten, iron, tin and indium. The conductor layer may be a single metal layer or an alloy layer, and examples of the alloy layer include layers formed from alloys of two or more metals selected from the above group (e.g., nickel-chromium alloy, copper-nickel alloy and copper-titanium alloy). Among these, from the viewpoints of versatility in forming the conductor layer, cost, ease of patterning, and the like, a single metal layer of chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver, or copper, or an alloy layer of a nickel-chromium alloy, a copper-nickel alloy, or a copper-titanium alloy is preferred, a single metal layer of chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver, or copper, or an alloy layer of a nickel-chromium alloy is more preferred, and a single metal layer of copper is even more preferred.

[0178] The conductor layer may be a single-layer structure or a multi-layer structure in which two or more single metal layers or alloy layers made of different kinds of metals or alloys are laminated. When the conductor layer has a multi-layer structure, the layer in contact with the insulating layer is preferably a single metal layer of chromium, zinc or titanium, or an alloy layer of a nickel-chromium alloy.

[0179] The thickness of the conductor layer depends on the desired design of the printed wiring board, but is generally 3 μm to 35 μm, and preferably 5 μm to 30 μm.

[0180] In one embodiment, the conductor layer may be formed by plating. For example, a conductor layer having a desired wiring pattern can be formed by plating the surface of the insulating layer by a conventionally known technique such as a semi-additive method or a full-additive method, and from the viewpoint of ease of production, it is preferable to form the conductor layer by the semi-additive method. An example of forming the conductor layer by the semi-additive method will be described below.

[0181] First, a plating seed layer is formed on the surface of an insulating layer by electroless plating. Next, a mask pattern is formed on the formed plating seed layer to expose a part of the plating seed layer corresponding to a desired wiring pattern. After a metal layer is formed on the exposed plating seed layer by electrolytic plating, the mask pattern is removed. Thereafter, unnecessary plating seed layer is removed by etching or the like to form a conductor layer having a desired wiring pattern.

[0182] [Semiconductor Devices] The semiconductor device of the present invention includes the printed wiring board of the present invention. The semiconductor device of the present invention can be manufactured by using the printed wiring board of the present invention.

[0183] Examples of the semiconductor device include various semiconductor devices used in electric appliances (for example, computers, mobile phones, digital cameras, and televisions) and vehicles (for example, motorcycles, automobiles, trains, ships, and aircraft).

[0184] The semiconductor device of the present invention can be manufactured by mounting a component (semiconductor chip) on a conductive portion of a printed wiring board. The "conductive portion" refers to a portion of a printed wiring board that transmits an electric signal, and the portion may be either on the surface or embedded. The semiconductor chip is not particularly limited as long as it is an electric circuit element made of semiconductor material.

[0185] The method of mounting a semiconductor chip when manufacturing a semiconductor device is not particularly limited as long as the semiconductor chip functions effectively, but specific examples include a wire bonding mounting method, a flip chip mounting method, a bumpless buildup layer (BBUL) mounting method, an anisotropic conductive film (ACF) mounting method, a non-conductive film (NCF) mounting method, etc. Here, the "bumpless buildup layer (BBUL) mounting method" refers to "a mounting method in which a semiconductor chip is directly embedded in a recess in a printed wiring board and the semiconductor chip is connected to the wiring on the printed wiring board." EXAMPLES

[0186] The present invention will be specifically described below with reference to examples. However, the present invention is not limited to the following examples. In the following description, "parts" and "%" representing amounts mean "parts by mass" and "% by mass", respectively, unless otherwise specified. Furthermore, the operations described below were performed in an environment of normal temperature and pressure, unless otherwise specified.

[0187] <Example 1: Preparation of resin composition 1> Ten parts of a bisphenol A type epoxy resin ("828US" manufactured by Mitsubishi Chemical Corporation, epoxy equivalent: about 180), 20 parts of a bisphenol AF type epoxy resin ("YL7760" manufactured by Mitsubishi Chemical Corporation, epoxy equivalent: about 238), 20 parts of a biphenyl type epoxy resin ("NC3000L" manufactured by Nippon Kayaku Co., Ltd., epoxy equivalent: about 269), 3 parts of a phosphazene resin ("SPH-100" manufactured by Otsuka Chemical Co., Ltd.), and 10 parts of a phenoxy resin ("YX7553BH30" manufactured by Mitsubishi Chemical Corporation, a 1:1 solution of MEK and cyclohexanone with a solid content of 30% by mass) were dissolved in 20 parts of MEK and 40 parts of solvent naphtha by heating with stirring. After cooling to room temperature, 94 parts of an active ester curing agent (DIC Corporation's "HPC-8000-65T", active group equivalent of about 223, toluene solution with 65% solids by mass), 10 parts of a phenolic curing agent (DIC Corporation's "LA-3018-50P", active group equivalent of about 151, 2-methoxypropanol solution with 50% solids by mass), 6 parts of a benzoxazine curing agent (JFE Chemical Corporation's "ODA-BOZ", MEK solution with 50% solids by mass, benzoxazine ring equivalent of about 218), and (meth)acrylate (Shin-Nakamura Chemical Co., Ltd.) were mixed. The mixture consisted of 12 parts of NK Ester A-DOG (manufactured by Johoku Chemical Industry Co., Ltd., molecular weight 326, (meth)acryloyl group equivalent 163), 0.5 parts of rust inhibitor (BT120, 1,2,3-benzotriazole, manufactured by Johoku Chemical Industry Co., Ltd.), 8 parts of curing accelerator (4-dimethylaminopyridine (DMAP, MEK solution with 5% solids by mass), 0.2 parts of polymerization initiator (Perbutyl C, manufactured by NOF Corporation), and spherical silica (average particle size 0.5 μm, specific surface area 5.9 m) surface-treated with a phenylaminosilane coupling agent (KBM573, manufactured by Shin-Etsu Chemical Co., Ltd.). 2 The mixture was mixed with 400 parts of ethyl acetate / g, Admatechs's "SOC2" and dispersed uniformly in a high-speed rotary mixer, and then filtered through a cartridge filter (ROKITECHNO's "SHP100") to prepare Resin Composition 1.

[0188] The BT120 has the structure shown below. [ka]

[0189] A-DOG has the structure shown below. [ka]

[0190] <Example 2: Preparation of resin composition 2> In Example 1, 0.5 parts of the rust inhibitor (1,2,3-benzotriazole, BT120, manufactured by Johoku Chemical Industry Co., Ltd.) was changed to 1.5 parts of an antioxidant (IRGANOX1010, pentaerythritol tetrakis(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate)) manufactured by Ciba Japan Co., Ltd. Resin composition 2 was prepared in the same manner as in Example 1 except for the above points.

[0191] IRGANOX1010 has the structure shown below. [ka]

[0192] <Example 3: Preparation of resin composition 3> In Example 1, 0.5 parts of the rust inhibitor (1,2,3-benzotriazole, BT120, manufactured by Johoku Chemical Industry Co., Ltd.) was changed to 1.5 parts of a light stabilizer (LA-63P, manufactured by ADEKA Corporation). Resin composition 3 was prepared in the same manner as in Example 1 except for the above.

[0193] LA-63P has the structure shown below. [ka]

[0194] <Example 4: Preparation of resin composition 4> In Example 1, 1) 20 parts of biphenyl type epoxy resin ("NC3000L" manufactured by Nippon Kayaku Co., Ltd., epoxy equivalent of about 269) was replaced with 20 parts of bixylenol type epoxy resin ("YX4000H" manufactured by Mitsubishi Chemical Co., Ltd., epoxy equivalent of about 190). 2) 94 parts of active ester curing agent (DIC Corporation's "HPC-8000-65T", active group equivalent of about 223, toluene solution with solid content of 65% by mass) was replaced with 86 parts of active ester curing agent (DIC Corporation's "EXB9416-70BK", methyl isobutyl ketone solution with non-volatile content of 70% by mass and active group equivalent of about 330). 3) 6 parts of a benzoxazine-based curing agent (JFE Chemical's "ODA-BOZ" MEK solution with a solid content of 50% by mass, benzoxazine ring equivalent of about 218) was replaced with 10 parts of a carbodiimide-based curing agent (Nisshinbo Chemical's "V-03", active group equivalent of about 216, toluene solution with a solid content of 50% by mass), 4) 0.5 parts of the rust inhibitor (BT120, 1,2,3-benzotriazole, manufactured by Johoku Chemical Industry Co., Ltd.) was changed to 6 parts of a blue pigment (Cyanine Blue 4920, manufactured by Dainichi Seika Co., Ltd.). Resin composition 4 was prepared in the same manner as in Example 1 except for the above.

[0195] Cyanine blue has the structure shown below. [ka]

[0196] <Example 5: Preparation of resin composition 5> In Example 4, 6 parts of the blue pigment (Cyanine Blue 4920, manufactured by Dainichiseika Chemicals Co., Ltd.) was changed to 6 parts of carbon black (NV-7-201, manufactured by Nippon Pigment Co., Ltd.). Resin composition 5 was prepared in the same manner as in Example 4 except for the above.

[0197] <Example 6: Preparation of resin composition 6> Five parts of a bisphenol A type epoxy resin ("828US" manufactured by Mitsubishi Chemical Corporation, epoxy equivalent: approximately 180), 20 parts of a biphenyl type epoxy resin ("NC3000L" manufactured by Nippon Kayaku Co., Ltd., epoxy equivalent: approximately 269), 25 parts of a bixylenol type epoxy resin ("YX4000H" manufactured by Mitsubishi Chemical Corporation, epoxy equivalent: approximately 190), 3 parts of a phosphazene resin ("SPH-100" manufactured by Otsuka Chemical Co., Ltd.), and 10 parts of a phenoxy resin ("YX7553BH30" manufactured by Mitsubishi Chemical Corporation, a 1:1 solution of MEK and cyclohexanone with a solid content of 30% by mass) were dissolved in 40 parts of MEK and 40 parts of toluene by heating with stirring. After cooling to room temperature, 94 parts of an active ester curing agent (DIC Corporation's "HPC-8000-65T", active group equivalent of about 223, toluene solution with 65% solids by mass), 10 parts of a phenolic curing agent (DIC Corporation's "LA-3018-50P", active group equivalent of about 151, 2-methoxypropanol solution with 50% solids by mass), 10 parts of a carbodiimide curing agent (Nisshinbo Chemical Inc.'s "V-03", active group equivalent of about 216, toluene solution with 50% solids by mass), 10 parts of a (meth)acrylate (Nihon Naka The mixture consisted of 17 parts of "NK Ester A-DOG" manufactured by Muramura Chemical Industry Co., Ltd., molecular weight 326), 0.5 parts of rust inhibitor (BT120, 1,2,3-benzotriazole manufactured by Johoku Chemical Industry Co., Ltd.), 8 parts of curing accelerator (4-dimethylaminopyridine (DMAP), MEK solution with 5% solids by mass), 0.2 parts of polymerization initiator (Perbutyl C manufactured by NOF Corporation), and spherical silica (average particle size 0.3 μm, specific surface area 30.7 m) surface-treated with a phenylaminosilane coupling agent (KBM573 manufactured by Shin-Etsu Chemical Co., Ltd.). 2 The mixture was mixed with 200 parts of dimethylformamide (1 / g, Denka Company's "UFP-30") and uniformly dispersed in a high-speed rotary mixer, and then filtered through a cartridge filter (ROKITECHNO Company's "SHP020") to prepare Resin Composition 6.

[0198] <Example 7: Preparation of resin composition 7> In Example 6, 0.5 parts of the rust inhibitor (BT120, 1,2,3-benzotriazole, manufactured by Johoku Chemical Industry Co., Ltd.) was changed to 1.5 parts of an antioxidant (IRGANOX1010, pentaerythritol tetrakis(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate)) manufactured by Ciba Japan Co., Ltd. Resin composition 7 was prepared in the same manner as in Example 6 except for the above points.

[0199] <Example 8: Preparation of resin composition 8> In Example 6, 0.5 parts of the rust inhibitor (BT120, 1,2,3-benzotriazole, manufactured by Johoku Chemical Industry Co., Ltd.) was changed to 1.5 parts of a light stabilizer (LA-63P, manufactured by ADEKA Corporation). Resin composition 8 was prepared in the same manner as in Example 6 except for the above.

[0200] <Example 9: Preparation of resin composition 9> In Example 6, 1) 20 parts of biphenyl type epoxy resin ("NC3000L" manufactured by Nippon Kayaku Co., Ltd., epoxy equivalent weight: approx. 269) was replaced with 20 parts of bisphenol AF type epoxy resin ("YL7760" manufactured by Mitsubishi Chemical Co., Ltd., epoxy equivalent weight: approx. 238). 2) The amount of phenol-based hardener (DIC "LA-3018-50P", active group equivalent of about 151, 2-methoxypropanol solution with 50% solids) was changed from 10 parts to 5 parts. 3) 10 parts of a carbodiimide-based curing agent (Nisshinbo Chemical's "V-03", active group equivalent of about 216, toluene solution with 50% solids by mass) was replaced with 10 parts of a benzoxazine-based curing agent (JFE Chemical's "ODA-BOZ", MEK solution with 50% solids by mass, benzoxazine ring equivalent of about 218). 4) 0.5 parts of the rust inhibitor (BT120, 1,2,3-benzotriazole, manufactured by Johoku Chemical Industry Co., Ltd.) was changed to 4 parts of a blue pigment (Cyanine Blue 4920, manufactured by Dainichi Seika Co., Ltd.). Resin composition 9 was prepared in the same manner as in Example 6 except for the above.

[0201] <Example 10: Preparation of resin composition 10> In Example 9, 6 parts of the blue pigment (Cyanine Blue 4920, manufactured by Dainichiseika Chemicals Co., Ltd.) was changed to 6 parts of carbon black (NV-7-201, manufactured by Nippon Pigment Co., Ltd.). Resin composition 10 was prepared in the same manner as in Example 9 except for the above.

[0202] <Comparative Example 1: Preparation of Comparative Resin Composition 1> 0.5 parts of the rust inhibitor (BT120, 1,2,3-benzotriazole, manufactured by Johoku Chemical Industry Co., Ltd.) was not used in Example 1. Comparative resin composition 1 was prepared in the same manner as in Example 1 except for the above points.

[0203] <Comparative Example 2: Preparation of Comparative Resin Composition 2> In Example 6, 0.5 parts of the rust inhibitor (BT120, 1,2,3-benzotriazole, manufactured by Johoku Chemical Industry Co., Ltd.) was not used. Comparative resin composition 2 was prepared in the same manner as in Example 6 except for the above points.

[0204] <Measurement of the average particle size of inorganic fillers> 100 mg of inorganic filler, 0.1 g of dispersant (SAN NOPCO "SN9228"), and 10 g of methyl ethyl ketone were weighed into a vial and dispersed by ultrasonic waves for 20 minutes. Using a laser diffraction particle size distribution measuring device (Shimadzu Corporation "SALD-2200"), the particle size distribution was measured by the batch cell method, and the average particle size was calculated based on the median diameter.

[0205] [Table 1] *In the table, "a1" represents the value obtained by dividing the mass of the (A) component by the epoxy equivalent, "e1" represents the value obtained by dividing the mass of the active ester curing agent by the active ester group equivalent, "e2" represents the value obtained by dividing the mass of the benzoxazine curing agent by the benzoxazine ring equivalent, "b2" represents the value obtained by dividing the mass of the (B) component by the (meth)acryloyl group equivalent, "e3" represents the content of the carbodiimide curing agent in the resin composition, and "b1" represents the content of the (B) component in the resin composition.

[0206] [Preparation of resin sheet] As a support, a PET film ("Lumirror R80" manufactured by Toray Industries, Inc., thickness 38 μm, softening point 130°C, hereinafter sometimes referred to as "release PET") that had been release-treated with an alkyd resin-based release agent ("AL-5" manufactured by Lintec Corporation) was prepared.

[0207] <Preparation of resin sheet A> In the resin compositions 1 to 5 and the comparative resin composition 1, each resin composition was uniformly applied onto a release PET film using a die coater so that the thickness of the resin composition layer after drying was 40 μm, and the resin composition layer was obtained on the release PET film by drying at 80 to 120°C (average 100°C) for 4 minutes. Next, a rough surface of a polypropylene film (Oji F-Tex Co., Ltd. "Alphan MA-411", thickness 15 μm) was laminated as a protective film on the surface of the resin composition layer that was not bonded to the release PET film so as to be bonded to the resin composition layer. This resulted in a resin sheet A consisting of the release PET (support), the resin composition layer, and the protective film in this order.

[0208] <Preparation of Resin Sheet B> In resin compositions 6 to 10 and comparative resin composition 2, the resin composition was uniformly applied onto a release PET sheet using a die coater so that the thickness of the resin composition layer after drying was 10 μm, and the resin composition layer was obtained on the release PET sheet by drying at 80° C. for 2 minutes. Next, a rough surface of a polypropylene film (Oji F-Tex Co., Ltd. "Alphan MA-411", thickness 15 μm) was laminated as a protective film on the surface of the resin composition layer not bonded to the support so as to be bonded to the resin composition layer. This resulted in a resin sheet B consisting of the release PET (support), the resin composition layer, and the protective film in this order.

[0209] [Measurement of dielectric tangent] The protective film was peeled off from the resin sheet A or B obtained in the examples and comparative examples, and the resin was heat-cured by heating at 200°C for 90 minutes, and the support was peeled off to obtain a sheet-like cured product. The cured product was cut into a length of 80 mm and a width of 2 mm to be used as an evaluation sample. The dielectric tangent of this evaluation sample was measured at a measurement frequency of 5.8 GHz and a measurement temperature of 23°C by the cavity resonance perturbation method using an HP8362B device manufactured by Agilent Technologies. Measurements were performed on three test pieces, and the average value was calculated.

[0210] [Haloing and peel strength measurement of plated conductor layer] <Preparation of samples for halo evaluation and peel strength measurement> (1) Surface preparation for inner layer circuit boards Both sides of a glass cloth-based epoxy resin double-sided copper-clad laminate (copper foil thickness 18 μm, substrate thickness 0.4 mm, Panasonic R1515A) with an inner layer circuit formed were etched 1 μm with a microetching agent (Mec CZ8101) to roughen the copper surface.

[0211] (2) Lamination of a resin sheet with a support The protective film was peeled off from each of the prepared resin sheets A and B, and the sheets were laminated on both sides of the inner layer circuit board using a batch type vacuum pressure laminator (MVLP-500, manufactured by Meiki Co., Ltd.). The lamination was performed by reducing the pressure for 30 seconds to 13 hPa or less, and then pressing for 30 seconds at 100°C and a pressure of 0.74 MPa.

[0212] (3) Curing of the resin composition The laminated resin sheet was cured at 130° C. for 30 minutes, followed by 170° C. for 30 minutes to cure the resin composition layer, thereby forming an insulating layer.

[0213] (4) Via hole formation In Examples 1 to 5 and Comparative Example 1, a CO2 laser processing machine (Hitachi Via Mechanics, LC-2E21B / 1C) was used to drill holes in the insulating layer under the conditions of a mask diameter of 1.60 mm, a focus offset value of 0.050, a pulse width of 25 μs, a power of 0.66 W, an aperture of 13, a shot number of 2, and a burst mode (10 kHz), forming multiple via holes such that the top diameter (diameter) of the via holes on the insulating layer surface was about 50 μm. Then, the release PET was peeled off.

[0214] In Examples 6 to 10 and Comparative Example 2, a CO2 laser processing machine (Mitsubishi Electric Corporation "605GTWIII(-P")) was used to drill holes in the insulating layer under the conditions of a mask diameter of 1 mm, a pulse width of 16 μs, energy of 0.2 mJ / shot, number of shots of 2, and burst mode (10 kHz), forming multiple via holes such that the top diameter (diameter) of the via holes on the insulating layer surface was approximately 30 μm. Then, the release PET was peeled off.

[0215] (5) Roughening treatment The inner layer circuit board with the insulating layer formed was immersed in swelling dip Securigant P (aqueous solution of glycol ethers and sodium hydroxide) containing diethylene glycol monobutyl ether manufactured by Atotech Japan as a swelling liquid at 60°C for 10 minutes, then immersed in Concentrate Compact P (aqueous solution of KMnO4: 60g / L, NaOH: 40g / L) manufactured by Atotech Japan as a roughening liquid at 80°C for 20 minutes, and finally immersed in Reduction Shalusin Securigant P (aqueous solution of sulfuric acid) manufactured by Atotech Japan as a neutralizing liquid at 40°C for 5 minutes, and then dried at 80°C for 30 minutes. This board was designated as evaluation board A.

[0216] (6) Semi-additive plating Evaluation substrate A was immersed in an electroless plating solution containing PdCl2 at 40°C for 5 minutes, and then immersed in an electroless copper plating solution at 25°C for 20 minutes. After heating at 150°C for 30 minutes to perform an annealing treatment, an etching resist was formed, and after forming a pattern by etching, copper sulfate electrolytic plating was performed to form a conductor layer with a thickness of 20 μm. Next, an annealing treatment was performed at 200°C for 60 minutes. This substrate was designated evaluation substrate B.

[0217] <Measurement of via hole dimensions, halo distance, and halo ratio after roughening treatment> A cross-section of the evaluation substrate A was observed using a FIB-SEM composite device ("SMI3050SE" manufactured by SII Nanotechnology Co., Ltd.). In detail, the insulating layer was cut out using a FIB (focused ion beam) so that a cross section parallel to the thickness direction of the insulating layer and passing through the center of the via bottom of the via hole appeared. This cross section was observed by SEM. The bottom diameter and top diameter of the via hole were measured from the observed image. In addition, in the image observed by SEM, a gap was observed that was formed by the insulating layer peeling off from the copper foil layer of the inner layer substrate, continuing from the edge of the via bottom. Therefore, from the observed image, the distance r1 from the center of the via bottom to the edge of the via bottom (corresponding to the inner radius of the gap) and the distance r2 from the center of the via bottom to the far end of the gap (corresponding to the outer radius of the gap) were measured, and the difference r2-r1 between these distances r1 and r2 was calculated as the halo distance from the edge of the via bottom at that measurement point.

[0218] The above measurement was performed on five randomly selected via holes. The average of the top diameters of the five measured via holes was adopted as the top diameter Lt of the sample after the roughening treatment. The average of the bottom diameters of the five measured via holes was adopted as the bottom diameter Lb of the sample after the roughening treatment. Furthermore, the average of the halo distances of the five measured via holes was adopted as the halo distance Wb from the edge of the via bottom of the sample.

[0219] From the measurement results, the taper ratio (the ratio of the top diameter Lt of the via hole after the roughening treatment to the bottom diameter Lb, "Lb / Lt") and the halo ratio Hb (the ratio of the halo distance Wb from the edge of the via bottom after the roughening treatment to the radius (Lb / 2) of the via bottom of the via hole after the roughening treatment, "Wb / (Lb / 2)") were calculated. If this halo ratio Hb was 35% or less, it was judged as "◯", and if the halo ratio Ht was more than 35%, it was judged as "×".

[0220] <Measurement and evaluation of adhesion (peel strength) between plated conductor layer> A 10 mm wide and 100 mm long cut was made in the conductor layer of evaluation board B, and one end of this was peeled off and held with a gripper (TSE Corporation, Autocom type testing machine AC-50C-SL). The load (kgf / cm) when 35 mm was peeled off vertically at a speed of 50 mm / min at room temperature was measured.

[0221] [Table 2]

[0222] In Examples 1 to 10, it was confirmed that even when components (E) to (I) were not contained, the results were similar to those of the above Examples, although to different degrees. [Explanation of symbols]

[0223] 100 Insulating layer 100U The surface of the insulating layer opposite the conductive layer 110 Beer Hall 120 Beer Bottom 120C Center of via bottom 130 Beer Top 140 Discolored area 150 Edge of via bottom of via hole 160 Gap 170 Outer edge of gap 180 Via top edge 190 Outer edge of discolored area 200 Inner layer board 210 Conductor layer Lb Bottom diameter of via hole Lt Top diameter of via hole Wb Halo distance from the edge of the via bottom

Claims

1. (A) an epoxy resin, (B) a (meth)acrylic acid ester, (C) a haloing inhibitor, and (D) an inorganic filler; The component (A) contains a liquid epoxy resin and a solid epoxy resin, The component (B) has a cyclic structure, The component (C) is any one of an azole compound rust inhibitor, a hindered phenol-based antioxidant, and a hindered amine-based light stabilizer, The content of the component (A) is 5% by mass or more and 20% by mass or less, when the total amount of non-volatile components in the resin composition is 100% by mass, The content of the (B) component is 1% by mass or more and 8% by mass or less, when the total amount of non-volatile components in the resin composition is 100% by mass, A resin composition, wherein the content of the component (C) is 0.01% by mass or more and 5% by mass or less, when the total amount of non-volatile components in the resin composition is 100% by mass.

2. The resin composition according to claim 1, wherein the component (B) has a structure represented by the following formula (B-1): 【Chemistry 1】 (In formula (B-1), R 1 and R 4 each independently represents an acryloyl group or a methacryloyl group; R 2 and R 3 each independently represents a divalent linking group; Ring A represents a divalent cyclic group.

3. The resin composition according to claim 1 or 2, further comprising (E) a curing agent.

4. 4. The resin composition according to claim 3, wherein the component (E) is at least one selected from the group consisting of a benzoxazine-based curing agent, a carbodiimide-based curing agent, a phenol-based curing agent, and an active ester-based curing agent.

5. The resin composition according to any one of claims 1 to 4, which is used for insulation purposes.

6. The resin composition according to any one of claims 1 to 5, which is for forming an insulating layer.

7. The resin composition according to any one of claims 1 to 5, which is a resin composition for forming an insulating layer for forming a conductor layer formed on an insulating layer.

8. The resin composition according to any one of claims 1 to 7, which is used for sealing semiconductor chips.

9. A resin sheet comprising a support and a resin composition layer provided on the support, the resin composition layer comprising the resin composition according to any one of claims 1 to 8.

10. A printed wiring board comprising an insulating layer formed from a cured product of the resin composition according to any one of claims 1 to 8.

11. A semiconductor device comprising the printed wiring board according to claim 10.

Citation Information

Patent Citations

  • Resin composition

    JP2014028880A

  • Resin composition

    JP2014034580A

  • Method for manufacturing printed-wiring board

    JP2014093355A

  • Curable resin composition, curable resin molded body, cured article, laminate, composite and multilayer printed board

    JP2016060809A